Solid-state stabilized sage essential oil liposomes in tamarind gum beads: dual encapsulation for modulating oxidative stress and energy homeostasis in postharvest Agaricus bisporus - Jia Wang; Lei Feng; Yueyuan Li; Yafang Yang; Xiangyou Wang; Yanyin Guo; Hiroaki Kitazawa; Tian Zhong; Ling Li (Food Hydrocolloids, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Precise dual-gene knockout of MSTN and SOCS2 via cytidine base editing enhances muscling and growth in goats - Ling Li; Ming-Xing Cao; Muhammad Farhab; Paing Oo Kyaw; Shu-Qi Zhao; Yi Zhao; Feng-Lei Chen; Tariq Sohail; Ejaz Ahmad; Shao-Xian Cao; Yu-Guo Yuan (Functional & Integrative Genomics, 2026)

A mechanism-constrained large language model-based intelligent diagnosis framework for bridge defects - Hui Jin; Si-Ming Zhou; Han Chen; Zhi-Yu Xie; Feng Li; Yong Li; Jian-Feng Zhu; Yi-Feng Ling; Zhi-Min Wu; Xiang-Ming Zhou (Engineering Structures, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Hierarchical transcription factor interaction network: RsrF mediates dual-layer regulation of plant-polysaccharide-degrading enzyme biosynthesis in fungus - Mei-Ling Pang; Wen-Tong Li; Ze-Yu Deng; Di Tian; Yan-Hao Zhao; Dian-Qi Wu; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (Bioresource Technology, 2026)

Thermally activated iron-rich Palygorskite for tetracycline hydrochloride removal via coupling adsorption and in situ Fenton-like oxidation - Chao Jiang; Rong Jiang; Ling Meng; Huiyu Li; Xiao Feng; Saeed Ahmed; Yongjun Feng (Applied Clay Science, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

The potential role of the Sox9a protein in regulating cyp19a transcription and ovarian development in the olive flounder (Paralichthys olivaceus) - Chang Shu; Lijuan Wang; Congcong Zou; Xungang Tan; Yuxia Zou; Zhihao Wu; Yan Liu; Qiaowan Wu; Ling Wang; Guoyu Wang; Ze Li; Feng You (Theriogenology, 2026)

The effect of thermal ultrasonic treatment on the interaction between tea polyphenols and goat milk proteins at different ratios - Nanqi Zhao; Yutong Ma; Xiaosong Feng; Wenbang An; Xin Wang; Lin Chen; Qingkun Zeng; Ling Li; Xianchao Feng (Food Chemistry, 2026)

Accelerated microbiome reconstruction and soil-like formation in graphite tailings by composite microbial agent CMA - Yanli An; Xilin Li; Ling Liu; Jijia Liu; Changbo Du; Youde Feng (Environmental Research, 2026)

Microbial-driven transformation of dissolved organic nitrogen in estuarine waters: mechanisms and environmental implications - Pengju Li; Jia Yang; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Environmental Research, 2026)

Environmental drivers of coordinated water-nitrogen management for maize resource use efficiency - Chenyan Li; Boyue Zhang; Xinlong Li; Xianqi Wang; Meiyi Feng; Shaozhong Kang; Taisheng Du; Ling Tong; Jian Kang; Jia Gao; Risheng Ding (European Journal of Agronomy, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Metal-phenolic microcapsules-reinforced hydrogel-based in situ tumor vaccine for postoperative adjuvant therapy - Xin Tan; Renwang Sheng; Yanling Liang; Yinghua Tao; Weikun Li; Nuoya Chen; Diyi Feng; Xinyang Pan; Shuangshuang Ma; Fangzhou Liu; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Land-use-driven terrestrial inputs and fresh-seawater mixing jointly shape sediment organic nitrogen in the Pearl River Estuary - Jia Yang; Pengju Li; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Shicheng Lin; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Science China Earth Sciences, 2026)

Fermented mackerel processing by-products and soybean meal as alternative protein source in diets of juvenile black rockfish (Sebastes schlegelii) - Yuyu Wang; Feng Liu; Yuanyuan Li; Ling Wang; Teng Ma; Junxia Wang; Jianjun Guo (Fish Physiology and Biochemistry, 2026)

Evaluation of fermentation performance of yeast strains isolated from Passiflora ligularis - Shuqing Feng; Qin Zhu; Jian Cai; Qingfang Xu; Jie Li; Qian Sun; Ying Mao; Ling Zhu (Archives of Microbiology, 2026)

Data-driven outcome prediction and rational resource allocation in severe traumatic brain injury: a multicenter retrospective study integrating survival analysis and machine learning ensembles - Shuyue Li; Xingzhi Liu; Jun Lei; Hao Lin; Min Li; Seidu A. Richard; Zhigang Lan; Ling Feng (Acta Neurologica Belgica, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

Unveiling small-scale tropical forest loss and post-loss recovery in the Congo Basin - Yihang Zhang; Xiaodong Li; Feng Ling; Xia Wang; Yun Du; Peter M. Atkinson (Global Environmental Change, 2026)

Porous matrix derived from steel slag for shape-stabilized phase change materials based on NaNO3 - Jinlong Cai; Mengxiao Tao; Tongtong Zhang; Jian Song; Dejian Pei; Yi Jin; Zushu Li; Feng Jiang; Xiang Ling (Chemical Engineering Journal, 2026)

Dynamic injectable and multifunctional hydrogel incorporating dihydroquercetin (DHQ)-loaded chitosan nanoparticles for sustained DHQ release and accelerated burn wound healing - De-yang Huo; Kai Zheng; Zhao-feng Tian; Ling-jie Song; Li-chun Zhao; Wei Li (Carbohydrate Polymers, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Correction: Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Short and long-term exposure to fine particulate matter, nitrogen dioxide and meteorological factor and the risk of glaucoma: evidence from the China health and retirement longitudinal study, distributed lag non-linear and Mendelian randomization models - Yeni Li; Ling Zhu; Miaomiao Lu; Manli Wu; Xiaoxu Zhang; Feng Shi; Xiaonan Li (International Journal of Biometeorology, 2026)

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

miR-13a-3p regulates susceptibility to Bacillus thuringiensis Cry1Ac protoxin in Ostrinia furnacalis by targeting OfβGRP3 and suppressing melanization - Shuzhong Li; Fuyun Li; Zitian Wang; Ling Fang; Zupeng Gao; Honglun Bi; Siquan Ling; Congjing Feng (Pesticide Biochemistry and Physiology, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

A new sesquiterpene lactone and other phytochemicals from the fruits of Magnolia grandiflora and their chemophenetic significance - Qiu-Ye Zhao; Zhen-Quan Li; Shi-Huan Yin; Hui-Ling Zhou; Xin-Ying Wang; Wei-Yang Feng; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Correction to: Altitudinal effects on soil microbial diversity and composition in qinghai spruce forests of qilian mountain - Yiming Feng; Changming Zhao; Ling Wang; Jinhua Li; Tianwei Wu; Chunyan Lv; Ming Jin (Plant and Soil, 2026)

Phytostabilization potential of Amorpha fruticosa for cadmium and copper in mining soils: tolerance mechanisms and migration control - Xin Zheng; Ling Lei; Huayan Huang; Yuyuan Ouyang; Li Long; Maohang Jia; Shuang Feng; Zaijin Sun; Heng Xu (Plant and Soil, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

Probiotics in the alleviation of food allergies in infants and young children: research progress - Zihan Wen; Zhenzhen Zhang; Xiaojing Li; Zhenxing Qiang; Hui Wang; Qiuying Wang; Junying Zhao; Wenxiao Feng; Jingjing Peng; Ling Guo; Lijun Chen (Critical Reviews in Food Science and Nutrition, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

AI weather prediction toward multi-scale earth system prediction: status and pathways - Jinglin Zhang; Qinghui Chen; Feng Zhang; Zeyi Niu; Zekai Zhang; Fenghua Ling; Bin Guo; Hailong Liu; Cong Bai; Gang Li; Renhe Zhang (Science Bulletin, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Selenylation enhances anti-melanogenic activity of polysaccharide from Cinnamomum cassia Presl. by regulating the CREB/MITF/tyrosinase pathway - Qi-Cong Chen; Ya-Li Wang; Yu Luo; Yan-Ling Zhang; Wen-Xin Li; Wei-Feng Cai; Qian Ni; Cui-Ping Jiang; Qiang Liu; Chun-Yan Shen (Food Research International, 2026)

In situ arming of NETs for targeted delivery of redox-modulating liposomes to eradicate intracellular bacteria in sepsis - Liya Yang; Na Yin; Tongge Wang; Ruilin Chao; Qiang Yang; Yifei Gao; Shenyao Jin; Yiman Chen; Jian Li; Ling Guo; Min Feng (Chemical Engineering Journal, 2026)

Altitudinal effects on soil microbial diversity and composition in qinghai spruce forests of qilian mountain - Yiming Feng; Changming Zhao; Ling Wang; Jinhua Li; Tianwei Wu; Chunyan Lv; Ming Jin (Plant and Soil, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Drivers and dynamics of urban green spaces in Africa: A remote sensing perspective in the 21st century(2000–2024) - Yuhong Huang; Lihui Wang; Li Yang; Paul Mapfumo; Evaristus M. Irandu; Yun Du; Feng Ling (Urban Forestry & Urban Greening, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

An AT-hook motif nuclear protein AHL13 interacts with Poly(ADP-ribose) to regulate Arabidopsis immunity - Jia Liu; Zhuo Chen; Ling Sun; Tingyan Huang; Yu Chen; Xiaohui Li; Hu Liu; Xinyi Huang; Yan Peng; Baomin Feng (Plant Science, 2026)

Five new prenylated flavonoids derivatives from Dysosma versipellis and their DPPH radical scavenging activity - Meng Zhang; Hong-Yun Bai; Ling-Yu Ye; Xiao-Ke Zheng; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Shen Liang; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry Letters, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Aeration strategy and nitrogen loading for stable partial nitrification coupled with oxygen-permeable membranes: Long-term performance, biofilm characteristics, and microbial succession - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Ling-Hu Li; Xin-Xin Sun; Yu-You Li; Rong Chen (Journal of Water Process Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Polyketides and drimane sesquiterpenoids from kiwi plant endophytic fungus Aspergillus flavus J302-03 with antibacterial and anti-inflammatory activities - Xin-Wen Luo; Fang-Lu Wei; Hong-Fei Li; Jin-Yao Mao; Yan-Ling Yang; Juan He; Tao Feng (Phytochemistry, 2026)

Antifungal phenolic glucosides and related congeners from the cold-seep-derived Talaromyces trachyspermus CS-106 - Xing-Yan Feng; Sui-Qun Yang; Xiao-Ming Li; Xin Li; Bin-Gui Wang; Ling-Hong Meng (Phytochemistry, 2026)

Effects of meteoric water–rock interaction on the quality of the Middle Jurassic reservoirs along the Hongciliang tectonic belt, Yabulai Basin, NW China - Shuangqi Feng; Hancheng Ji; Liang Chen; Xuegui Jiang; Pengfei Xiang; Yanqing Shi; Chunfu Liao; Ying Liu; Ling Li (Journal of Asian Earth Sciences, 2026)

Ni/Cu-Impregnated Pd membrane reactor for enhanced Water-Gas shift reaction - Peijun Li; Yeqing Ling; Yanling Feng; Duanhao Wang; Tao Li; Rui Xiao (Fuel, 2026)

The PAH-AM-PEG-ApoE@siRNA Nanocarrier Delivery System for Polo-like Kinase 1 Inhibition Suppresses Glioma Progression - Feng Su; Shengnan Lu; Junli Zhang; Yu Zhang; Yaoyao Zhang; Ling Cheng; Jing Li; Ying Li; Guangwei He; Lifang Yin (AAPS PharmSciTech, 2026)
The poor efficacy of chemotherapy for glioma is mainly due to the difficulty of drug penetration through the blood–brain barrier (BBB), as well as the difficulty of drug concentration in the tumor tissue to reach the effective therapeutic level. The emerging tumor-targeted delivery technology can facilitate the precise enrichment of drugs in the tumor site. Apolipoprotein E (ApoE(159–167) 2 ) binds to low-density lipoprotein receptor-related protein 1 (LRP-1) on the blood–brain barrier and helps it to specifically cross the BBB. Based on this, in this study, poly (ethylene glycol) (PEG) dimerized with ApoE(159–167) 2 was used for the modification of PAH-AM, and amphiphilic PAH-AM-PEG-ApoE nanocarriers were successfully prepared. Among them, the PEG modification could effectively prolong the retention time of the nanoparticles in vivo and reduce the toxic side effects, while the ApoE(159–167) 2 polypeptide could specifically penetrate the blood–brain barrier for intracerebral targeted delivery by binding to LRP-1. The nanocarrier further binds to small interfering RNA (siRNA) targeting PLK1 , a key cell cycle factor, by electrostatic interaction to construct the nano-delivery system PAPA@siPLK1. In vitro experiments showed that the nanoparticles significantly inhibited the proliferation of U87MG glioma cells, induced apoptosis, and specifically silenced the mRNA and protein expression of PLK1 . The results of in vivo animal experiments showed that PAPA@siPLK1 could effectively inhibit tumor growth and had potential brain permeability; The PAPA@siPLK1 nanocarrier delivery system developed in this study achieves PLK1 gene silencing through efficient siRNA delivery, providing an important basis for novel therapeutic strategies for glioma.

Brain functional basis of the association between positive expectation and acupuncture efficacy in knee osteoarthritis - Ze-Yi Wang; Cun-Zhi Liu; Xiao-Ya Wei; Na Zhang; Jin-Ling Li; Chihkai Lee; Hang Zhou; Jian-Feng Tu; Xu Wang (Brain Imaging and Behavior, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Two new naphthopyrones and a new prenylisoflavone from Berchemia lineata - Ling Li; Lin Feng; Lihua Peng; Weilin Qiao; Wei Li; De-an Guo (Phytochemistry Letters, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

Integrating legume rotation and optimal nitrogen management enhances cotton yield and mitigates greenhouse gas emissions in a jujube-cotton intercropping system - Tiantian Li; Lu Feng; Jinbin Wang; Zhengjun Cui; Hang Qiao; Qiang Hu; Nan Cao; Ling Li; Wei Zhang; Mingwei Du; Yaru Zhao; Gulinigaer Taxi; et al. (European Journal of Agronomy, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Impacts of acidification and warming on carbon sequestration capacity in Pacific oysters: Roles of biosynthesis and biodeposition - Zi-Jing Meng; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Ping Li; Zhi-Hua Li (Aquaculture, 2026)

Deciphering thermal behaviors of Qingchuan bitumen: Effects of atmosphere, heating rate, sample weight, kerogen, and clay minerals - Xianghui Zhang; Yuanyu Kou; Qin Liu; Huan Yang; Wei Hu; Xiangqi Leiyu; Hailong Wan; Wenling Yang; Xinyu Li; Junjie Wang; Ling Wang; Qian Feng (Fuel, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Coalescent 2D heterostructure for high-efficient surface-enhanced Raman scattering and electrochemical sensing - Muhammad H. Nawaz; S. Santhoshkumar; Thi H. Ho; Balamurugan Arumugam; Mohamed Gamal Mohamed; Tuan V. Vu; Yousra.M. Nabil; Mohammed G. Kotp; Li-Wei Tu; Hung-Duen Yang; Ahmed F.M. EL-Mahdy; Shiu-Ming Huang; et al. (Chemical Engineering Journal, 2026)

Single-stage wet sieving: an optimized protocol for rapid and accurate particle size analysis of fine-grained soils - Shun Yi; Yue Zhu; Jia-jun Pan; Xi-ling Guo; Yue-feng Zhou; Yan-li Wang (CATENA, 2026)

Terrestrial in situ cosmogenic nuclide production rate scaling models: Theory, progress, and prospects - Jie Zhou; Weijian Zhou; Yunchong Fu; Feng Xian; Du Wang; Xianlin Yang; Guocheng Dong; Li Zhang; Ling Tang; Guoqing Zhao; Mengyu Zang (Science China Earth Sciences, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Smartphone-integrated luminescent Europium-organic framework sensor for on-off ratiometric identification of levofloxacin in water and milk samples - Lei-Ming Dai; Ling Li; Sheng-Yong You; Li Zhang; Mei-Feng Wu; Ji-Yong Zou (Analytica Chimica Acta, 2026)

Chemical and biological mechanisms of wild-type, multidrug-resistant bacteria inactivation via low-dose UVA/Fe²⁺/peracetic acid treatment - Qing Li; Ling Feng; Zhuochu Liu; Stefanos Giannakis (Water Research, 2025)

Contrast of composition and sources of PM2.5 and PM10 in Shenzhen, China: Revealing key factors on health risks - Xing Peng; Li He; Ling-Yan He; Jiang-Yao Tan; Ke-Jin Tang; Wen-Jie Yu; Wen-Wei He; Xiao-Feng Huang (Journal of Environmental Management, 2025)

Spatial distribution and source apportionment of antibiotics in aquaculture and reserve zones of Yellow River Delta: Risk assessments and priority ranking - Zhenni Su; Feng Liu; Ling Zhao; Huiyun Zou; Xuewen Li (Journal of Environmental Chemical Engineering, 2025)

Reducing the allergenicity of αs1-casein by Lactiplantibacillus plantarum JY067 fermentation - Kai Dong; Shiyu Liu; Shihang Li; Yue Su; Feng Zhao; Ling Guo; Yujun Jiang; Xinyan Yang (Food Research International, 2025)

A computationally driven screening-construction-mechanism strategy of magnetic molecularly imprinted polymers for aliphatic aldehydes detection - Yongqing Zhang; Xiaolong Shang; Jiaqi Guo; Ling Ao; Caihong Shen; Miao Liu; Feng Lin; Wenxian Li; Liqiang Zhang; Baoguo Sun; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

From mung bean to Minglv-flavor baijiu: Unraveling the signature aroma profile and aging dynamic - Ruijuan Wang; Lijun Yan; Feng Ding; Shanshan Xu; Weiqi Hu; Ling Zhang; Boyang Xu; Hao Zhou; Dongdong Mu; Xingjiang Li (Food Chemistry, 2025)

Colloidal stability of Salvia officinalis essential oil nano-liposomes and its antioxidant and antibacterial dual effect in postharvest preservation of Agaricus bisporus - Jia Wang; Xin Jiang; Lei Feng; Jiali Han; Yueyuan Li; Xiangyou Wang; Hiroaki Kitazawa; Yanyin Guo; Ling Li (Food Control, 2025)

Synergistic enhancement of nitrate selectivity in electrodialysis under high salinity via membrane hydrophobic modification and mass transfer optimization - Ling Feng; Hanfei Li; Feiyu He; Binghui Tian; Min Yang (Desalination, 2025)

Amino-functionalized electrospinning separator tailors desolvation kinetics and Zn2+ transport for high-performance aqueous zinc-ion batteries - Zhuoqun Liu; Luxin Yu; Zhenying Zhang; Yang Feng; Bin Li; Yingqiao Jiang; Ningning Zhao; Jing Zhu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

Geochemical investigations on black shale weathering profiles in contrasting terrains: Role of topography on chemical weathering - Junjie Feng; Wei Wei; Sixiang Ling; Xiaoning Li; Chunwei Sun; Xin Liao; Xiyong Wu (CATENA, 2025)

G Proteins-Associated Dose-Dependent Effects of Oxytocin on Oxytocin Neuronal Activity and Astrocytic Plasticity of the Supraoptic Nucleus - Xiao-Yu Liu; Shuo Ling; Yang Liu; Yunhao Jiang; Xiaoran Wang; Shuwei Jia; Chunmei Hou; Yanpeng Li; Delai Qiu; Yu-Feng Wang (Molecular Neurobiology, 2025)

Design of a ball screw for the electric control rod drive mechanism in nuclear reactors - Chaoqun Qian; Yi Ou; Yongjun Bai; Changguang Zhou; Ling Li; Junwan Shen; Hutian Feng; Jian Wu (Annals of Nuclear Energy, 2025)

Estimating and compensating for shear-wave splitting in orthotropic media - Hai-feng Chen; Peng-yuan Sun; Xiang-yang Li; Zhong-ping Qian; Jian-lei Zhang; Gui-ling Zhao; Xiao-ying Qin (Applied Geophysics, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Norsesquiterpenes from the stems and leaves of Pinellia pedatisecta Schott - Xu Chen; Yan-gang Cao; Fang-Ge Chi; Yan-ling Liu; Kai-li Ye; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Mapping long-term surface water dynamics by integrating fine resolution binary maps and medium resolution fraction series - Zirui Wang; Yuhong Huang; Xiaofeng Jia; Zhen Hao; Sisi Li; Liang Zhang; Yun Du; Feng Ling (Journal of Hydrology, 2025)

Using HRMS fingerprinting to elaborate the effects of reclaimed water irrigation on small-molecule distribution in rice - Keng-Jui Lin; Wen-Ling Chen; Feng-Wen Chen; Yu-Chien Cho; Jin-Jing Lee; Shan-Li Wang (Journal of Environmental Management, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Surface display of the protective antigen FlaB of Vibrio anguillarum in Lactobacillus plantarum PO23 and its immune response in Paralichthys olivaceus - Jixing Feng; Minghui Liu; Ling Liu; Jian Zhang; Xuepeng Li; Hongye Wang (Fish & Shellfish Immunology, 2025)

Emissions and carbon isotopic signatures of polycyclic aromatic compounds (PAHs, OPAHs) produced by coking in China - Jiajie Li; Ling Mu; Xiaofan Li; Xiaofeng Liu; Huiling Bai; Chuanyang Feng; Xin Jiang; Ying Wei; Chenhui Li (Environmental Pollution, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Identifying Risk Transition Pattern of Compound Flooding Using the Copula Integrated Markov Chain - Xiaodi Li; Ming Zhong; Xueyou Li; Jiao Wang; Lu Zhuo; Feng Ling; Lixiang Song; Xianwei Wang; Jinhui Li; Xiaohong Chen (Water Resources Management, 2025)

Chromium Mitigates the Iron-Induced Glucose Metabolism Disorder via the PI3K/Akt/Bcl-2 Signaling Pathway: An In Vivo Study in Wistar Rats - Haotian Xun; Lu Ma; Boqian Feng; Yunlong Ma; Yu Zhao; Faxuan Wang; Liping Li; Yi Zhao; Ling Fan (Biological Trace Element Research, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

PFOA and a dash of aluminum: The perfect recipe for growing drug-resistant biofilms in urban water supply - Bowei Li; Ling Feng; Jiajia Zhang; Stefanos Giannakis (Journal of Hazardous Materials, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Humic substances initiated superior photochemical pollutant conversion in environmentally relevant matrices: When ZnO met MoS2 as electron mediator - Jia-Sheng Li; Song Hu; Ling-Feng Wang; Wei Da; Ai-Yong Zhang; Lu Zhao; Jing-Yu Zhang (Journal of Environmental Chemical Engineering, 2025)

Synergistic regulatory mechanisms of plant hormone combinations on the growth and lipid accumulation of Chlorella pyrenoidosa in saline wastewater - Qiao-Ling Zhao; Kai-Yuan Li; Jia-Qi Xi; Jin-Long Zhou; Dan-Ni Miao; Zeng-Ling Ma; Ying Zhang; Hai-Jun Luo; Feng Gao (Journal of Environmental Chemical Engineering, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Root and foliar uptake, bidirectional translocation, subcellular distribution, and metabolism of tire wear particle-derived p-phenylenediamines and their quinones in Chinese cabbage and bok choy - Yan Wang; Hanyi Li; Feng Tan; Ling N. Jin; Junrong Su; Chunling Luo (Environmental Pollution, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Constructing core collections of sorghum for Jiang-flavor Baijiu production in Chishui River Basin - Lei Li; Feng Jiang; Li Wang; Qiao-Ling Zhang; Qing-Fan Ren; Zhen-Yu Zhao; Fan Yang (Genetic Resources and Crop Evolution, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Gut microbiota induces host midgut immune response and contributes to defending against Bt Cry1Ac protoxin in Ostrinia furnacalis - Shuzhong Li; Zitian Wang; Fuyun Li; Ling Fang; Zhaoyang Han; Honglun Bi; Congjing Feng (Journal of Invertebrate Pathology, 2025)

Phytohormone-augmented microalgae: A dual-functional solution for pharmaceutical contaminants removal and resource recovery - Jun-Jie Gu; Xiao-Xiao Dou; Jin-Long Zhou; Si-Yuan Guo; Ashiwin Vadiveloo; Xiao-Ling Zhang; Kai-Yuan Li; Dong-Zhi Chen; Feng Gao (Journal of Hazardous Materials, 2025)

Molecular mechanisms underlying multi-generational skeletal abnormalities in marine medaka induced by the quinolone antibiotic norfloxacin (NOR) - Cun-Long Wang; Ping Li; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Study on the impact of microplastic characteristics on ecological function, microbial community migration and reconstruction mechanisms during saline-alkali soil remediation - Yifei Li; Wei Ling; Jian Yang; Yi Xing; Qi Zhang; Lihui Feng; Jiachen Hou; Chang Hou; Qingbin Lu; Tianqi Wu; Ziyuan Gao; Yifei Li (Journal of Hazardous Materials, 2025)

Efficiency of microbial fermentation on microbial shifts, enzymatic activity, and transcriptions in black soldier fly larvae during the sugarcane waste conversion - Fareed Uddin Memon; ChiHo Li; Sheraz Ahmad; Ying Cui; Xingbao Feng; Peng Zeng; Farhan Nabi; Zhijun Huang; Gianluca Tettamanti; Ting Chen; Ling Tian (Environmental Pollution, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Stagnant waters mobilize hidden dangers: How PFOA and metal pollutants foster pathogen growth and antimicrobial resistance spread - Bowei Li; Ling Feng; Sofia Samoili; Stefanos Giannakis (Chemical Engineering Journal, 2025)

Flexible and ultra-high electromagnetic interference shielding films with fiber-bridged segregated conductive network - Jia-Le Zhang; Sheng Yong; Tong Wang; Jie Feng; Jie Li; Yue-Yi Wang; Ling Xu; Gan-Ji Zhong; Jun Lei; Ding-Xiang Yan; Zhong-Ming Li (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Procyanidin B2 mitigate asthmatic airway remodeling by inhibiting TGF-β1-induced airway smooth muscle proliferation through ROS signaling - Wenyan Liang; Mingzhen Zhang; Hongyu Wang; Ling Feng; Dengke Li; Ruizhi Hao; Weiping Xie; Xiaoning Zeng; Yuan Ma (Tissue and Cell, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

The potential electrical transmission mechanism of strengthening petroleum hydrocarbon biodegradation by KOH-modified biochar - Wen Li; Quanwei Song; Jufeng Li; Xianyuan Du; Jiacai Xie; Zhongyuan Li; Xing Chen; Nan Zhao; Feng Ju; Hao Ling (Journal of Environmental Chemical Engineering, 2025)

CSSF: Collaborative spatial-spectral fusion for generating fine-resolution land cover maps from coarse-resolution multi-spectral remote sensing images - Zhixiang Yin; Xinyan Li; Penghai Wu; Jie Lu; Feng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

Polycationic nanoparticles for cascaded antibiosis and LPS- detoxifying via co-delivery of antibiotics and TLR siRNA in bacterial infected diseases treatment - Yufeng Zhang; Yini Huangfu; Ling Xu; Zhezhe Zhao; Qi Su; Hui Li; Yumin Zhang; Chuangnian Zhang; Pingsheng Huang; Anjie Dong; Zujian Feng; Weiwei Wang (Chemical Engineering Journal, 2025)

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Effects of ultrasonic treatment on protein in goat milk: Changes in structure and function and enhancement of heat-sterilized protein function - Yutong Ma; Rui Li; Shan Qian; Sijing Yuan; Qingkun Zeng; Pan Yang; Ling Li; Xianchao Feng; Lin Chen (International Dairy Journal, 2025)

Rhizosphere endophytes as allies in plant defense against heavy metals and organic pollutants in soil: Advances and applications - Sicheng Hang; Chen Wu; Guanwei Peng; Feng Li; Fei Ge; Jie Gan; Ling Li; Jie Li (Applied Soil Ecology, 2025)

Gut microbiota modulation: a narrative review on a novel strategy for prevention and alleviation of ovarian aging - Wei Lyu; De-Feng Li; Shu-Ying Li; Hua Hu; Jian-Yun Zhou; Ling Wang (Critical Reviews in Food Science and Nutrition, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Fate of polystyrene micro- and nanoplastics in zebrafish liver cells: Influence of protein corona on transport, oxidative stress, and glycolipid metabolism - Ling Liu; Yanan Xu; Yuqing Ma; Fengshang Duan; Cunlong Wang; Jianxue Feng; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Unveiling spatiotemporal patterns and key drivers of soil conservation from a “historical-future-intervention” perspective: A case study of the Danjiangkou Reservoir Area, China - Pengcheng Zhao; Lihui Wang; Xiaodi Zheng; Yang Li; Lijie Lu; Yunjie Yang; Jinliang Huang; Yun Du; Feng Ling (Journal of Environmental Management, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

β-Hydroxybutyrate ameliorated metabolic dysfunction and improved synaptic integrity via AKT signaling in an LPS-induced depression mice model - Shengnan Mou; Tahir Ali; Li Ling; Jinxing Feng; Shupeng Li (Food Bioscience, 2025)

Duplicate CgCREBL2β involved in the response of oyster upon high-temperature stress through the induction of glycolysis and haemocyte apoptosis - Lei Gao; Qingsong Li; Ling Wang; Jiayu Ye; Xingyi Feng; Hairu Xu; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2025)

An ultrafast dual-channel ratiometric fluorescence probe based on functionalized N-GQDs for dynamic monitoring of salicylic acid in plants - Hou-Yun Huang; A-ling Tang; Feng Gao; Shuai Tan; Zhi-Min Rao; Li-Wei Liu; Shi-Tao Liu; Xiang Zhou; Lin-Lin Yang; Song Yang (Chemical Engineering Journal, 2025)

Adaptive laboratory evolution induces cell wall alterations for succinic acid tolerance in Saccharomyces cerevisiae - Ling Qin; Shoujie He; Jin Hou; Guangjian Li; Yunzi Feng; Mouming Zhao; Mingtao Huang (Bioresource Technology, 2025)

Acute toxicity, bioconcentration, and metabolomic profiling of agrochemical organosilicone spray adjuvants in Zebrafish - Tianyou Feng; Jianling Liu; Ling Wu; Yuanqiang Luo; Ling Liu; Fen Li; Guangbin Wu; Ping Lu; Yuping Zhang (Aquatic Toxicology, 2025)

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

The Impact of Microplastics on Adsorption of Chlorophenols by River-Suspended Sediments - Shiqi Tao; Simin Feng; Yuyun Chen; Ting Duan; Zengyu Liu; Ling Li; Rongrong Yun; Chayma Chilouch (Environmental Management, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

SmGRAS5 acts as a positive regulator in GA-induced biosynthesis of tanshinones in Salvia miltiorrhiza hairy roots - Wenrui Li; Suyu Lin; Ruihong Wang; Chen Chen; Qiliang Huang; Feng Ling; Zongsuo Liang (Plant Science, 2025)

Unravelling the fouling behavior of cation exchange membrane (CEM) by waste salt containing decyltrimethylammonium chloride during membrane electrolysis - Ling Feng; Binghui Tian; Li Chen; Min Yang (Environmental Research, 2025)

Red light-emitting diode irradiation delays the senescence of postharvest pakchoi through promoting antioxidant capacity and regulating ascorbate-glutathione cycle - Feng Guo; Ying Sun; Huali Hu; Hongsheng Zhou; Yingtong Zhang; Xuesong Liu; Jun Ling; Shufen Luo; Pengxia Li (Postharvest Biology and Technology, 2025)

Mineral-dependent release, migration and enrichment of toxic elements during black shale weathering: An integrated study from profile scale to mineral scale - Wei Wei; Sixiang Ling; Xiaoning Li; Chunwei Sun; Junjie Feng; Jiawei Luo; Xiyong Wu; Chuan He (Journal of Hazardous Materials, 2025)

Highly synergistic degradation of norfloxacin and outstanding elimination of antibiotic-resistant elements by a combined electro-Fenton/peracetic acid process under mild conditions - Ling Feng; Wentao Dong; Bowei Li; Qing Li; Zhijing Liu; Ruirui Feng; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

The structures of two polysaccharides from Fructus Corni and their protective effect on insulin resistance - Guang-Yuan Ma; Lu-Kuan Hou; Jia-Hui Guo; Jing-Chun Sun; Qiuna Nong; Yu-Fan Wang; Sheng-Wei Hu; Wen-Jing Zhao; Jin Tan; Xiao-Feng Liu; Yuan Guo; Bo-Jing Zhang; et al. (Carbohydrate Polymers, 2025)

Understanding equilibrium climate sensitivity changes from CMIP5 to CMIP6: Feedback, AMOC, and precipitation responses - Xinqi Wang; Lijuan Li; He Wang; Ling Zuo; Bin Wang; Feng Xie (Atmospheric Research, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Regulatory networks of bZIPs in drought, salt and cold stress response and signaling - Yanli Yang; Yi Xu; Baozhen Feng; Peiqian Li; Chengqi Li; Chen-Yu Zhu; Shu-Ning Ren; Hou-Ling Wang (Plant Science, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

Sex-specific effects of triphenyltin on gut microbiota and intergenerational effects in marine medaka (Oryzias melastigma) - Ping Li; Bian-Hao Zeng; Shu-Wen He; Bin Liu; Cheng-Zhuang Chen; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Association between air temperature exposure and childhood rhinitis risk, and the mediating role of ambient O3: A multi-city study of 40,103 Chinese preschool children - Zhiping Niu; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Jing Wei; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Uncertainty analysis and parameter optimization of a water yield ecosystem service model: A case study of the Qilian Mountains, China - Bei Wang; Gao-Feng Zhu; Jun-Tao Zhong; Chun-Feng Ma; Ling Zhang; Mei-Bao Tan; Xin Li (Science of The Total Environment, 2025)

Quartz luminescence chronology reveals late Holocene coastal dune development in South China and its correlation with regional sea level fluctuations - Jianhui Jin; Junjie Wei; Zhiyong Ling; Zhizhong Li; Feng Jiang; Chenyang Hou; Daiyu Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Multifunctional microneedle patch synergized with electrical stimulation to regulate microenvironment for enhanced healing of infected diabetic wounds - Weikun Li; Xin Tan; Yanling Liang; Nuoya Chen; Diyi Feng; Yinghua Tao; Tao Liu; Xiaojing Wu; Huiqing Lu; Ling Liu; Feiling Feng; Liqin Ge (Chemical Engineering Journal, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

Source-pathway-sink framework to guide surface bacterial risk assessment and control in residential bathroom - Qisheng Li; Huan Liu; Lumeng Liu; Ling Jin; Shuwan Wang; Tian Ma; Yingxian Zhai; Jinghui Xin; Xiongwei Miao; Qifeng Fan; Chi Feng; Meng Liu (Building and Environment, 2025)

Biotransport and toxic effects of micro- and nanoplastics in fish model and their potential risk to humans: A review - Yanan Xu; Ling Liu; Yuqing Ma; Cunlong Wang; Fengshang Duan; Jianxue Feng; Haiyang Yin; Le Sun; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Aquatic Toxicology, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

Effects of FGFR2b-ligand signaling on pancreatic branching morphogenesis and postnatal islet function - Li-Li Jin; Yi-Ling Yin; Fei-Wei Li; Yu-Mei Zhou; Wen Chen; Ye Tian; Xiao Feng; Yi Xu; Peng-Fei Chen; Jin-San Zhang; Hui-Jing Xu (Journal of Molecular Histology, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

Establishing effective learning bridge cross multi-scale feature maps for object detection and semantic segmentation - Bo Wang; Zeyu Feng; Jun Li; Qinghong Sheng; Xiao Ling; Xiang Liu; Haowen Wang (International Journal of Remote Sensing, 2025)

Exposure to outdoor humid-heat and indoor dampness-mold during infancy is associated with increased childhood asthma risk: A large-scale multi-city study in Chinese preschool children - Zhiping Niu; TianYi Chen; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

New insights into ultrasound-assisted noncovalent nanocomplexes of β-lactoglobulin and neochlorogenic acid/cryptochlorogenic acid and its potential application for curcumin loading - Fang Li; Taijiao Xiang; Lie Jiang; Yong Cheng; Gongshuai Song; Danli Wang; Tinglan Yuan; Ling Li; Feng Chen; Zisheng Luo; Jinyan Gong (Food Research International, 2025)

The aroma transformation of Japanese sea bass (Lateolabrax japonicas) through endogenous enzyme incubation during the lag phase of attached microorganisms - Xinru Liu; Junlan Guan; Yuanfan Yang; Ling Wu; Hui Ni; Qingbiao Li; Feng Chen (Food Chemistry, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Recent progress and perspectives of single-atom catalysts with framework architecture for zinc-air battery cathodes - Zekun Zhang; Jia Dong; Chunting Huang; Kexin Wan; Zemin Feng; Bin Li; Ningning Zhao; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

Constructing chromium-tolerance La0.6Sr0.4Co0.2Fe0.8O3-δ cathode for solid oxide fuel cells using entropy-assisted surface engineering - Xu Han; Qi Shao; Kaixin Li; Yuan Gao; Bo Wei; Zimin Cai; Kun Zheng; Peizhong Feng; Zhe Lv; Yihan Ling (Chemical Engineering Journal, 2025)

Activation of protein kinase B rescues against thapsigargin-elicited cardiac dysfunction through regulation of NADPH oxidase and ferroptosis - Xiaohu Wang; Feng-Juan Li; Yong Cheng; Shuying Chen; Shuyi Zhu; Yingmei Zhang; Russel J. Reiter; Milad Ashrafizadeh; Jie Lin; Guizhen Wang; Ling Lin; Jun Ren (Chemico-Biological Interactions, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Multi-omics Analysis Reveals Key Gut Microbiota and Metabolites Closely Associated with Huntington’s Disease - Shu-Xia Qian; Yu-Feng Bao; Xiao-Yan Li; Yi Dong; Xiao-Ling Zhang; Zhi-Ying Wu (Molecular Neurobiology, 2025)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

Ion-exchange induced multiple effects to promote uranium uptake from nonmarine water by micromotors - Linhui Fu; Kai Feng; Qianqian Li; Mengting Qin; Jing Yang; Xinle Zhang; Ling Chen; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Corrigendum to “Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism” [J Hazard Mater Vol 480, 2024, 136236] - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhihua Li (Journal of Hazardous Materials, 2024)

Multigenerational effects of combined exposure of triphenyltin and micro/nanoplastics on marine medaka (Oryzias melastigma): From molecular levels to behavioral response - Jian-Xue Feng; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Cun-Long Wang; Ya-Nan Xu; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Construction of pyrimidine derivatives-copper enzyme mimics as colorimetric sensing elements for efficient detection of phenolic compounds and hydrogen peroxide - Tong-Qing Chai; Jia-Xin Li; Guo-Ying Chen; Mao-Ling Luo; Feng-Qing Yang (Journal of Hazardous Materials, 2024)

Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Crouching bacteria, hidden tetA genes in natural waters: Intracellular damage via double persulfate activation (UVA/Fe2+/PDS) effectively alleviates the spread of antibiotic resistance - Zhuochu Liu; Ling Feng; BoWei Li; Changwei Lü; Jiquan Sun; Stefanos Giannakis (Journal of Hazardous Materials, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Environmental behavior and toxic effects of micro(nano)plastics and engineered nanoparticles on marine organisms under ocean acidification: A review - Ling Liu; Haiyang Yin; Yanan Xu; Bin Liu; Yuqing Ma; Jianxue Feng; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

The spatial variations and driving factors of C, N, P stoichiometric characteristics of plant and soil in the terrestrial ecosystem - Wen-Lan Feng; Jin-Ling Yang; Li-Gang Xu; Gan-Lin Zhang (Science of The Total Environment, 2024)

Comparison of bipolar membrane electrodialysis, electrodialysis metathesis, and bipolar membrane electrodialysis multifunction for the conversion of waste Na2SO4: Process performance and economic analysis - Ming Zhu; Feiyu He; Ling Feng; Yongzhi Chi; Yu-You Li; Binghui Tian (Journal of Environmental Management, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Preparation of functionalized porous chitin carbon to enhance the H2O2 production and Fe3+ reduction properties of Electro-Fenton cathodes for efficient degradation of RhB - Chengwang Zhao; Wei Li; Jiashuo Hu; Chen Hong; Yi Xing; Hao Wang; Wei Ling; Yijie Wang; Lihui Feng; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Environmental Research, 2024)

Advanced thermal prediction for green roofs: CNN-LSTM model with SSA optimization - Jun Wang; Ding Xu; Wansheng Yang; Ling Lai; Feng Li (Energy and Buildings, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

Antiallodynic and antihyperalgesic effects of decursin associated with correcting mitochondrial dysfunction and oxidative stress in type 1 diabetic mice - Li Ma; You-Ya Fan; Ben-Ling Li; Feng Xu; Xin Zhao (Chemico-Biological Interactions, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

A novel dual-ligand copper-based nanoflower for the colorimetric and fluorescence detection of 2,4-dichlorophenol, epinephrine and hydrogen peroxide - Jia-Xin Li; Tong-Qing Chai; Guo-Ying Chen; Mao-Ling Luo; Jian-Bo Wan; Feng-Qing Yang (Analytica Chimica Acta, 2024)

Ratio Drought Index (RDI): A soil moisture index based on new NIR-red triangle space - Zhe Dong; Ling Wang; Maofang Gao; Xicun Zhu; Wenbin Feng; Nan Li (International Journal of Remote Sensing, 2024)

Generation and emission mechanism of polycyclic aromatic hydrocarbon (PAHs) during the coking process in Shanxi, China - Ziye Liu; Ling Mu; Chuanyang Feng; Xiaofan Li; Tian Liu; Xin Jiang; Huiling Bai; Xiaofeng Liu (Science of The Total Environment, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Preparation of a novel ATP liposome and its regulation of postharvest senescence in Agaricus bisporus - Xin Jiang; Jiali Han; Lei Feng; Jia Wang; Cunkun Chen; Hiroaki Kitazawa; Xiangyou Wang; Yanyin Guo; Ling Li (Food Bioscience, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Theoretical analysis of naproxen reaction with sulfate and hydroxyl radicals in the aqueous phase: Investigating reactive sites and reaction kinetics - Ji-Feng Yang; Wan-Li You; Deng You; Li-Ying Zheng; Jun-Ling Jin; Sheng-Lian Luo (Chemosphere, 2024)

Sustainable urban road planning under the digital twin-MCDM-GIS framework considering multidisciplinary factors - Feng Jiang; Junda Li; Ling Ma; Zejiao Dong; Weiwei Chen; Tim Broyd; Guohao Wang (Journal of Cleaner Production, 2024)

Remediation of petroleum-contaminated site soil by bioaugmentation with immobilized bacterial pellets stimulated by a controlled-release oxygen composite - Sheng Zhao; Ling-ling Li; Yue-jie Wang; Zheng-wei Liu; Shuai Yang; Xiang Gao; Chang-yun Zhang; An-feng Yu (Environmental Pollution, 2024)

Integrating RTM-GWAS and meta‑QTL data revealed genomic regions and candidate genes associated with the first fruit branch node and its height in upland cotton - Junji Su; Dandan Li; Wenmin Yuan; Ying Li; Jisheng Ju; Ning Wang; Pingjie Ling; Keyun Feng; Caixiang Wang (Theoretical and Applied Genetics, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Investigation of Toxoplasma gondii Infection in Yunnan Semi-fine Wool Sheep (Ovis aries) and wild Rodents in Yunnan, China - Zhao Li; Wen-Jie Cheng; Cai-Qin Deng; Meng-Ling Deng; Hai-Bo Peng; Xing-Quan Zhu; Feng-Cai Zou (Acta Parasitologica, 2024)

Research on the Flow-Induced Vibration of Cylindrical Structures Using Lagrangian-Based Dynamic Mode Decomposition - Xueji Shi; Zhongxiang Liu; Tong Guo; Wanjin Li; Zhiwei Niu; Feng Ling (Journal of Marine Science and Engineering, 2024)
An oscillating flow past a structure represents a complex, high-dimensional, and nonlinear flow phenomenon, which can lead to the failure of structures due to material fatigue or constraint relaxation. In order to better understand flow-induced vibration (FIV) and coupled flow fields, a numerical simulation of a two-degrees-of-freedom FIV in a cylinder was conducted. Based on the Lagrangian-based dynamic mode decomposition (L-DMD) method, the vorticity field and motion characteristics of a cylinder were decomposed, reconstructed, and predicted. A comparison was made to the traditional Eulerian-based dynamic mode decomposition (E-DMD) method. The research results show that the first-order mode in the stable phase represents the mean flow field, showcasing the slander tail vortex structure during the vortex-shedding period and the average displacement in the in-line direction. The second mode predominantly captures the crossflow displacement, with a frequency of approximately 0.43 Hz, closely matching the corresponding frequency observed in the CFD results. The higher dominant modes mainly capture outward-spreading, smaller-scale vortex structures with detail displacement characteristics. The motion of the cylinder in the in-line direction was accompanied by symmetric vortex structures, while the motion of the cylinder in the crossflow direction was associated with anti-symmetric vortex structures. Additionally, crossflow displacement will cause a symmetrical vortex structure that spreads laterally along the axis behind the cylinder. Finally, when compared with E-DMD, the L-DMD method demonstrates a notable advantage in analyzing the nonlinear characteristics of FIV.

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Resolving data gaps in global surface water monthly records through a self-supervised deep learning strategy - Zhen Hao; Xiaobin Cai; Yong Ge; Giles Foody; Xinyan Li; Zhixiang Yin; Yun Du; Feng Ling (Journal of Hydrology, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Decrypting the skeletal toxicity of vertebrates caused by environmental pollutants from an evolutionary perspective: From fish to mammals - Cun-Long Wang; Ping Li; Bin Liu; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Environmental Research, 2024)

Zero-strain Co-doped Na2FeP2O7/carbon delivers superior rate capability and long-cycle stability for sodium ion batteries - Jianhong Gao; Ziwei Chen; Wei Cao; Jiale Chen; Ming Zhang; Feng Lin; Yongsheng Li; Waqar Ahmad; Min Ling; Chengdu Liang; Jun Chen (Chemical Engineering Journal, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Fabrication of amidoxime grafted polyacrylonitrile for iodine vapor capture from off-gas - Ling Zhang; Mengfang Li; Xuan Liu; Jiaqi Feng; Yujia Liu; Yazhu Tu; Shuyang Li; Tao Duan (Chemical Engineering Journal, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Improving the Short-Range Precipitation Forecast of Numerical Weather Prediction through a Deep Learning-Based Mask Approach - Jiaqi Zheng; Qing Ling; Jia Li; Yerong Feng (Advances in Atmospheric Sciences, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Fatty acids metabolism in ozone-induced pulmonary inflammatory injury: Evidence, mechanism and prevention - Mengyuan Li; Xiangbing Kong; Xiaotong Jian; Yacong Bo; Xinyi Miao; Huaiyong Chen; Pingping Shang; Xiaolei Zhou; Ling Wang; Qiao Zhang; Qihong Deng; Yuan Xue; et al. (Science of The Total Environment, 2024)

Sustained release of a novel bilayer packaging film loaded with binary microemulsion of melatonin/pummelo essential oil and its regulation of postharvest energy metabolism in Agaricus bisporus - Lei Feng; Na Zhang; Jia Wang; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Cunkun Chen; Yanyin Guo (Food Control, 2024)

Fe-Doped CoNi layered hydrogencarbonate hierarchical Nano-Array assisted growth of ZIF-67 as an efficient OER/UOR bifunctional catalyst reaction for Overall Urea-Water electrolysis - Hongwen Tang; Zeyu Sun; Shuyan Fan; Siwen Feng; Ling Li; Ling Fang; Cuijuan Wang (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

Identifying the geospatial relationship of surface ozone pollution in China: Implications for key pollution control regions - Yong Cheng; Yan Peng; Li-Ming Cao; Xiao-Feng Huang; Ling-Yan He (Science of The Total Environment, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Purification and recovery of NaCl from epoxy resin waste salt through an integrated process based on aqueous two-phase systems (ATPS) - Ling Feng; Binghui Tian; Li Chen; Min Yang (Journal of Environmental Chemical Engineering, 2024)

Exposure to per- and polyfluoroalkyl substances in lung cancer patients and their associations with clinical health indicators - Si-Nan Huang; Ying-Hua Hu; Ting-Ting Xu; Yu-Ling Luan; Li-Xi Zeng; Zi-Feng Zhang; Ying Guo (Environmental Pollution, 2024)

High capacity and long service in sodium-ion batteries achieved by the refinement of BiOCl from lamellar to flower-like in ether electrolyte - Sheng-Li Wei; Yan-Ling Yang; Xiao-Lei Shi; Yu Sun; Jin-Geng Chen; Xue-Feng Tian; Yuan-Ting Wu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Residual networks without pooling layers improve the accuracy of genomic predictions - Zhengchao Xie; Xiaogang Xu; Ling Li; Cuiling Wu; Yinxing Ma; Jingjing He; Sidi Wei; Jun Wang; Xianzhong Feng (Theoretical and Applied Genetics, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Effects of the combined use of kaolinite and dolomite as catalysts for the heavy oil oxidation - Yanqiu Dai; Xianghui Zhang; Runlin Pu; Wei Hu; Ling Wang; Huan Yang; Wenlin Yang; Qin Liu; Ruyan Wang; Zhongquan Li; Qian Feng (Applied Clay Science, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Methyl contributes to the directed phosphorus doping of g-C3N4: pH-dependent selective reactive oxygen species enable customized degradation of organic pollutants - Zhanpeng Zhou; Hao Zeng; Ling Li; Rongdi Tang; Chengyang Feng; Daoxin Gong; Ying Huang; Yaocheng Deng (Water Research, 2024)

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

In vitro assessment of cytotoxicity of spent fluid catalytic cracking refinery catalysts on cell lines and identification of critical toxic metals - Yue-jie Wang; Zhi-guo Sheng; Jun Li; Zhen-feng Zhao; Ling-ling Li; Chen Shen (Toxicology in Vitro, 2024)

Paraflavitalea pollutisoli sp. nov., Pollutibacter soli gen. nov. sp. nov., Polluticoccus soli gen. nov. sp. nov., and Terrimonas pollutisoli sp. nov., four new members of the family Chitinophagaceae from polluted soil - Ze-Shen Liu; Xiao-Kang Wang; Ke-Huan Wang; Mei-Ling Yang; De-Feng Li; Shuang-Jiang Liu (Systematic and Applied Microbiology, 2024)

Characteristics of Trypsin genes and their roles in insecticide resistance based on omics and functional analyses in the malaria vector Anopheles sinensis - Xiang-Ying Li; Feng-Ling Si; Xiao-Xiao Zhang; Yu-Juan Zhang; Bin Chen (Pesticide Biochemistry and Physiology, 2024)

Environmental cadmium inhibits testicular testosterone synthesis via Parkin-dependent MFN1 degradation - Tian-Tian Wang; Hua-Long Zhu; Kong-Wen Ouyang; Hua Wang; Ye-Xin Luo; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Jin Zhang; Wei Chang; Qi Lu; Yu-Feng Zhang; et al. (Journal of Hazardous Materials, 2024)

Maternal prednisone exposure during pregnancy elevates susceptibility to osteoporosis in female offspring: The role of mitophagy/FNDC5 alteration in skeletal muscle - Zun-Yu Du; Hua-Long Zhu; Wei Chang; Yu-Feng Zhang; Qing Ling; Kai-Wen Wang; Jin Zhang; Quan-Bing Zhang; Xiu-Li Kan; Qu-Nan Wang; Hua Wang; Yun Zhou (Journal of Hazardous Materials, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Catalytic hydroconversion of residue from methanolysis of XilinGol League No. 6 Lignite: Cracking mechanism of C-O bond and structural features of liquid coal derivative - Sheng Li; Xiao-Yu Zhang; Zhi-Min Zong; Zhi-Hao Ma; Jian-Feng Shan; Xing-Shun Cong; Mei-Ling Xu; Li Li; Xian-Yong Wei (Fuel, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

Multiple-state pattern encrypted superhydrophobic-icephobic colorimetric sensing film for anticounterfeiting and food freshness monitoring - Huilin Dong; Xiaoya Sun; Haichao Li; Deqiang Li; Zhe Ling; Sheng Chen; Yanglei Xu; Feng Xu (Chemical Engineering Journal, 2024)

Establishing an efficient micropropagation method for Astragalus membranaceus (Huang Qi) - Thi Ngoc Anh Tran; Feng-Jiao Xu; Jae-Heung Ko; Deok-Chun Yang; Yingping Wang; Li Ling; Dong-Uk Yang; Seok-Kyu Jung (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Identification of a novel HIV-1 third-generation circulating recombinant form (CRF126_0755) in Guangdong, China - Yun Lan; Ruolei Xin; Ruiying He; Feng Li; Xuemei Ling; Linghua Li; Fengyu Hu (Archives of Virology, 2024)
The genetic recombination patterns and genetic distribution of HIV-1 are valuable for elucidating the epidemic and genetic diversity of HIV. Numerous HIV-1 circulating recombinant forms (CRFs) have recently emerged and disseminated rapidly. In China, at least 32 CRFs have been reported to account for more than 80% of all HIV infections. However, CRFs derived from the CRF07_BC and CRF55_01B lineages have never been recorded. Here, a novel third-generation CRF involving HIV-1 was identified in four HIV-1-infected patients in Guangdong, China, who had no epidemiological association with each other. Phylogenetic and recombinant analyses confirmed that these strains shared highly similar recombination patterns, with the CRF07_BC backbone substituted by a CRF55_01B segment; therefore, these strains were classified as CRF126_0755. This is the first study of a CRF derived from CRF07_BC and CRF55_01B. Bayesian phylogenetic inference suggested that CRF126_0755 originated in approximately 2005-2007. The present findings reveal that the genotype composition of HIV-1 has become more complex than that of other viruses and highlight the urgent need for continuous molecular screening and epidemic surveillance within HIV-1-infected populations to advance our understanding of viral transmission mechanisms.

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

Endophytic Stenotrophomonas geniculata KJ-6 via producing antifungal volatile organic compounds effectively control Lanzhou lily postharvest diseases - Lijun Ling; Yuanyuan Wang; Jialin Li; Wenting Cheng; Rui Yue; Lijun Feng; Yao Li; Yongpeng Zhou; Lu Lu (Food Bioscience, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Dual effect of organic/inorganic artificial protective layer to construct high-performance zinc metal anode - Yingxiao Du; Ruotong Li; Tingting Wang; Ziyi Feng; Han Dong; Fangfang Fan; Dezhao Deng; Jing Zhu; Yongguang Liu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2024)

Advances in Atmospheric Radiation: Theories, Models, and Their Applications. Part II: Radiative Transfer Models and Related Applications - Hua Zhang; Feng Zhang; Lei Liu; Yuzhi Liu; Husi Letu; Yuanjian Yang; Zhengqiang Li; Kun Wu; Shuai Hu; Ming Li; Tie Dai; Fei Wang; et al. (Journal of Meteorological Research, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

Potential Effects of Orally Ingesting Polyethylene Terephthalate Microplastics on the Mouse Heart - Tao Lu; Desheng Li; Xiaoqing Yuan; Zhenzhen Wang; Zhuang Shao; Xiaotian Feng; Chen Yang; Huan Liu; Guanqing Zhang; Yue Wang; Xiaohan Liu; Ling Zhou; et al. (Cardiovascular Toxicology, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

Identification of odor-causing compounds in six species of odor-producing microalgae separated from drinking water source with distinct fishy odor: Insight into microalgae growth and odor characteristics - Qingyuan Guo; Qingqin Meng; Ling Wang; Jianwei Yu; Xiao Chen; Dunxi Liu; Dasheng Li; Chunmiao Wang; Feng Liang; Weixing Ma; Zhaoxia Li; Cheng Ding (Chemosphere, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Long-term tralopyril exposure results in endocrinological and transgenerational toxicity: A two-generation study of marine medaka (Oryzias melastigma) - Bin Liu; Ping Li; Ren-Yan Du; Cun-Long Wang; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

Can environmental information disclosure spur corporate green innovation? - Enhui Feng; Yim Ling Siu; Christina W.Y. Wong; Shuangshuang Li; Xin Miao (Science of The Total Environment, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Utilising standard samples instead of randomly collected food waste in composting: Implementation strategy and feasibility evaluation - Jufei Wang; Chao Li; Mukesh Kumar Awasthi; Samuel Mbugua Nyambura; Zhenming Zhu; Hua Li; Jialiang Xu; Xuebin Feng; Xueru Zhu; Asad Syed; Ling Shing Wong; Wei Luo (Journal of Environmental Management, 2024)

Effects of Dendrobium officinale on physicochemical and flavor properties of yogurt during different fermentation time - Ling Li; Xusheng Shao; Ziyun Feng; Weihong Ni; He Jiang; Xianyue Gong; Gongnian Xiao (Food Bioscience, 2024)

Influence on the release of arsenic and tungsten from sediment, and effect on other heavy metals and microorganisms by ceria nanoparticle capping - Qi Li; Ling Liu; Wenming Yan; Xiang Chen; Ruiyan Liu; Ziyi Zhao; Feng Jiang; Yanfen Huang; Shunting Zhang; Yiqian Zou; Chenjun Yang (Environmental Pollution, 2024)

Mechanisms underlying palmitic acid-induced disruption of locomotor activity and sleep behavior in Drosophila - Yumei Huang; Jiaqi Zhang; Dongdong You; Shangqin Chen; Zhongdong Lin; Boyang Li; Menglai Ling; Haibin Tong; Feng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Functional characterization of genes related to triterpene and flavonoid biosynthesis in Cyclocarya paliurus - Shuang-yan Zhang; Yu-qing Peng; Gui-sheng Xiang; Wan-ling Song; Lei Feng; Xin-yue Jiang; Xue-jiao Li; Si-mei He; Sheng-chao Yang; Yan Zhao; Guang-hui Zhang (Planta, 2024)

Ucp4 Knockdown of Cerebellar Purkinje Cells Induces Bradykinesia - Ya-Yun Wang; Hui Liu; Shu-Jiao Li; Ban Feng; Yun-Qiang Huang; Shui-Bing Liu; Yan-Ling Yang (Molecular Neurobiology, 2024)
Although uncoupling protein 4 (UCP4) is the most abundant protein reported in the brain, the biological function of UCP4 in cerebellum and pathological outcome of UCP4 deficiency in cerebellum remain obscure. To evaluate the role of Ucp4 in the cerebellar Purkinje cells (PCs), we generated the conditional knockdown of Ucp4 in PCs ( Pcp2 cre ;Ucp4 fl/fl mice) by breeding Ucp4 fl/fl mice with Pcp2 cre mice. Series results by Western blot, immunofluorescent staining, and triple RNAscope in situ hybridization confirmed the specific ablation of Ucp4 in PCs in Pcp2 cre ;Ucp4 fl/fl mice, but did not affect the expression of Ucp2 , the analog of Ucp4 . Combined behavioral tests showed that Pcp2 cre ;Ucp4 fl/fl mice displayed a characteristic bradykinesia in the spontaneous movements. The electromyogram recordings detection excluded the possibility of hypotonia in Pcp2 cre ;Ucp4 fl/fl mice. And the electrical patch clamp recordings showed the altered properties of PCs in Pcp2 cre ;Ucp4 fl/fl mice. Moreover, transmission electron microscope (TEM) results showed the increased mitochondrial circularity in PCs; ROS probe imaging showed the increased ROS generation in molecular layer; and finally, microplate reader assay showed the significant changes of mitochondrial functions, including ROS, ATP, and MMP in the isolated cerebellum tissue. The results suggested that the specific knockdown of mitochondrial protein Ucp4 could damage PCs possibly by attacking their mitochondrial function. The present study is the first to report a close relationship between UCP4 deletion with PCs impairment, and suggests the importance of UCP4 in the substantial support of mitochondrial function homeostasis in bradykinesia. UCP4 might be a therapeutic target for the cerebellar-related movement disorder. Graphical Abstract

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Correction to: Small nucleolar RNA Snora73 promotes psoriasis progression by sponging miR‑3074‑5p and regulating PBX1 expression - Lihua Zhang; Hui Guo; Xiaoguang Zhang; Ling Wang; Feng Wei; Yike Zhao; Bo Wang; Yibo Meng; Yanling Li (Functional & Integrative Genomics, 2024)

Small nucleolar RNA Snora73 promotes psoriasis progression by sponging miR-3074-5p and regulating PBX1 expression - Lihua Zhang; Hui Guo; Xiaoguang Zhang; Ling Wang; Feng Wei; Yike Zhao; Bo Wang; Yibo Meng; Yanling Li (Functional & Integrative Genomics, 2024)
Chronic psoriasis is a kind of immune-mediated skin illness and the underlying molecular mechanisms of pathogenesis remain incompletely understood. Here, we used small RNA microarray assays to scan the differential expressed RNAs in psoriasis patient samples. The downstream miRNAs and its targets were predicted using bioinformatics analysis from online bases and confirmed using fluorescence in situ hybridization and dual‑luciferase report gene assay. Cell ability of proliferation and migration were detected using CCK-8 and transwell assays. The results showed that a new snoRNA Snora73 was upregulated in psoriasis patient samples. Overexpression of Snora73 significantly increased psoriasis cells viability and migration, while knockdown of Snora73 got the opposite results. Mechanistically, our results showed that Snora73 acted as a sponge for miR-3074-5p and PBX1 is a direct target of miR-3074-5p in psoriasis cells. Furthermore, miR-3074-5p suppressed psoriasis cell proliferation and migration, while PBX1 promoted cell proliferation and migration in psoriasis. Collectively, these findings reveal a crucial role of Snora73 in progression of psoriasis through miR-3074-5p/PBX1 signaling pathway and suggest a potential therapeutic strategy.

The remediation potential and kinetics of Pb2+ adsorbed by the organic frameworks of Cladophora rupestris - Lu-sheng Zhang; Xiao-yu Feng; Chang-fa Qiu; Ling-sheng Li; Yu Sun; Xin-yi Tao; Xin-yue Li; Zhao-wen Liu; De-ju Cao (Environmental Science and Pollution Research, 2024)

A latest progress in the study of fish behavior: cross-generational effects of behavior under pollution pressure and new technologies for behavior monitoring - Jian-Xue Feng; Ping Li; Yuan Liu; Ling Liu; Zhi-Hua Li (Environmental Science and Pollution Research, 2024)

Overall integrated navigation based on satellite and lidar in the standardized tall spindle apple orchards - Weihong Liu; Wenwei Li; Han Feng; Jiawei Xu; Shenghui Yang; Yongjun Zheng; Xingxing Liu; Zimeng Wang; Xiaokang Yi; Yichuan He; Ling Zhou (Computers and Electronics in Agriculture, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

High incidence of multiple intI1 genomic gene cassettes in Aeromonas strains - Bo Ling; Wei Feng; Nuo Yang; Lixia Fan; Guiying Guo; Xuesong Li; Jifeng Zeng; Jiping Zheng (Aquaculture, 2024)

Liquid crystal monomers in soils near the e-waste recycling site and liquid crystal display manufacturer: Exponential decrease with distance - Jiong-Feng Xie; Gao-Ling Wei; Li-Xi Zeng; Liang-Ying Liu (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Atmospheric CO2 controls on the MIS 6 glaciation: 10Be chronology of moraines in the Haizishan area, southeastern Tibetan Plateau - Guocheng Dong; Weijian Zhou; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Climatic factors and fertilization rates co-regulate anaerobic methane oxidation driven by multiple electron acceptors in Chinese paddy fields - Wang-ting Yang; Wei-qi Wang; Evgenios Agathokleous; Ya-nan Bai; Shuai Zhang; Chun Wang; Yan-fang Feng; Jia-qi Liu; Yu-ling Yang; Cai-yu Geng; Li-dong Shen (Journal of Cleaner Production, 2024)

Towards people-centric smart cities: A comparative evaluation of citizens’ sense of gain in pilot cities in China - Lugang Yu; Dezhi Li; Ling Mao; Shenghua Zhou; Haibo Feng (Journal of Cleaner Production, 2024)

Effects of different ohmic heating treatments on parvalbumin structure and reduction of allergenicity in Japanese eel (Anguilla japonica) - Xiaomin Li; Yun Deng; Weiqiang Qiu; Yuhui Feng; Yingshan Jin; Lanming Chen; Li Li; Ashily Ling Wang; Ningping Tao; Yinzhe Jin (Food Chemistry, 2024)

Sources of atmospheric oxygenated volatile organic compounds in different air masses in Shenzhen, China - Zhi-Jie Li; Ling-Yan He; Hao-Nan Ma; Xing Peng; Meng-Xue Tang; Ke Du; Xiao-Feng Huang (Environmental Pollution, 2024)

Elucidating influences of defects and thermal treatments on CO2 capture of a Zr-based metal–organic framework - Shan He; Ling-Xiao Li; Li-Tian Zhang; Shanshan Zeng; Chunmei Feng; Xiao-Xian Chen; Hao-Long Zhou; Xiao-Chun Huang (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Mycobacterium tuberculosis virulence protein ESAT-6 influences M1/M2 polarization and macrophage apoptosis to regulate tuberculosis progression - Feng Sun; Jiangbo Li; Ling Cao; Cunzi Yan (Genes & Genomics, 2024)

Moraxella haemolytica sp. nov., isolated from a goat with respiratory disease - Fu-Xiang Li; Wen-Hua Zhao; Zhan-Hong Li; Jian-Ling Song; Hua-Feng Gao (Archives of Microbiology, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Gut microbes consume host energy and reciprocally provide beneficial factors to sustain a symbiotic relationship with the host - Ying Wu; Liang Peng; Pengya Feng; Rong Han; Aman Khan; Sourabh Kulshreshtha; Zhenmin Ling; Pu Liu; Xiangkai Li (Science of The Total Environment, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

Can China's carbon intensity constraint policies improve carbon emission performance? Evidence from regional carbon emissions - Xin Miao; Enhui Feng; Yim Ling Siu; Shuangshuang Li; Christina W.Y. Wong (Journal of Environmental Management, 2023)

Properties of an active film based on glutenin/tamarind gum and loaded with binary microemulsion of melatonin/pummelo essential oil and its preservation for Agaricus bisporus - Lei Feng; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Yanyin Guo; Xinru Dong; Haipeng Liu (Food Chemistry, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Bioleaching of metals from spent fluid catalytic cracking catalyst using adapted Acidithiobacillus caldus - Yue-jie Wang; Ling-ling Li; Shen Zhao; Yan Chen; An-feng Yu (Environmental Science and Pollution Research, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Correction: Anti-Inflammatory Mechanism of Walnut Meal Peptide/ Ellagic Acid Nanoparticles on LPS-Stimulated RAW264.7 Cells by Inhibition of NFκB and MAPK Activation - Yuxi Ling; Yanxia Feng; Ziqi Li; Le Cheng; Xuan Zhang; Difeng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Essential and non-essential elements in tuna and billfish around the world: Distribution patterns and influencing factors - Jingqian Xie; Qiang Wu; Ling Tao; Feng Wu; Shuyi Tu; Duofu Chen; Tian Lin; Tiejun Li (Marine Pollution Bulletin, 2023)

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

CD44 targeting nanodrug based on chondroitin sulfate for melanoma therapy by inducing mitochondrial apoptosis pathways - Yan Li; Huiwen Hou; Zengmei Liu; Wen Tang; Jie Wang; Lu Lu; Jiaai Fu; Didi Gao; Feiyan Zhao; XinQing Gao; Peixue Ling; Fengshan Wang; et al. (Carbohydrate Polymers, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Anti-Inflammatory Mechanism of Walnut Meal Peptide/ Ellagic Acid Nanoparticles on LPS-Stimulated RAW264.7 Cells by Inhibition of NF-κB and MAPK Activation - Yuxi Ling; Yanxia Feng; Ziqi Li; Le Cheng; Xuan Zhang; Difeng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Configured quantum reservoir computing for multi-task machine learning - Wei Xia; Jie Zou; Xingze Qiu; Feng Chen; Bing Zhu; Chunhe Li; Dong-Ling Deng; Xiaopeng Li (Science Bulletin, 2023)

Mitigating greenhouse gas emissions by replacing inorganic fertilizer with organic fertilizer in wheat–maize rotation systems in China - Yajin Hu; Donghao Li; Yong Wu; Siyuan Liu; Ling Li; Weiqiang Chen; Shufang Wu; Qingxiang Meng; Hao Feng; Kadambot H.M. Siddique (Journal of Environmental Management, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Emission factors and source profiles of VOCs emitted from coke production in Shanxi, China - Ling Mu; Chuanyang Feng; Yangyong Li; Xiaofan Li; Tian Liu; Xin Jiang; Ziye Liu; Huiling Bai; Xiaofeng Liu (Environmental Pollution, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Adenine phosphate-Cu nanozyme with multienzyme mimicking activity for efficient degrading phenolic compounds and detection of hydrogen peroxide, epinephrine and glutathione - Tong-Qing Chai; Guo-Ying Chen; Ling-Xiao Chen; Jia-Li Wang; Chun-Yan Zhang; Feng-Qing Yang (Analytica Chimica Acta, 2023)

Contactin-associated protein-like 2 antibody-associated autoimmune encephalitis in children: case reports and systematic review of literature - Yong-kang Cheng; Yao-zheng Ling; Chun-feng Yang; Yu-mei Li (Acta Neurologica Belgica, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

The relationship between extreme ambient temperature and small for gestational age: A cohort study of 1,436,480 singleton term births in China - Xiang Li; Jing Ma; Yang Cheng; Ling Feng; Shaoshuai Wang; Guanpeng Dong (Environmental Research, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

The Dynamics of Dopamine D2 Receptor-Expressing Striatal Neurons and the Downstream Circuit Underlying L-Dopa-Induced Dyskinesia in Rats - Kuncheng Liu; Miaomiao Song; Shasha Gao; Lu Yao; Li Zhang; Jie Feng; Ling Wang; Rui Gao; Yong Wang (Neuroscience Bulletin, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Hydrodynamic and anthropogenic disturbances co-shape microbiota rhythmicity and community assembly within intertidal groundwater-surface water continuum - Ze Zhao; Lu Zhang; Guoqing Zhang; Han Gao; Xiaogang Chen; Ling Li; Feng Ju (Water Research, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

Impacts of calcium peroxide on phosphorus and tungsten releases from sediments - Xiang Chen; Ling Liu; Wenming Yan; Minjuan Li; Qi Li; Xiangyu He; Ziyi Zhao; Ruiyan Liu; Shunting Zhang; Yanfen Huang; Feng Jiang (Environmental Research, 2023)

Distribution characteristics of secondary organic aerosol tracers in PM2.5 in Jinzhong - Ling Mu; Xin Jiang; Yangyong Li; Xuemei Li; Xiaofan Li; Tian Liu; Ziye Liu; Chuanyang Feng (Atmospheric Environment, 2023)

Three-Dimensional Numerical Study of Dam-Break Flood Impacting Problem with VOF Method and Different Turbulence Closures - Ling Peng; Ting Zhang; Jianzhu Li; Ping Feng (Water Resources Management, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Emission characteristics of benzene series in FCC flue gas - Bohan Wang; Sen Li; DongXu Sun; Jiawei Bian; Hai Zhao; Hong Li; Yang Zhang; Feng Ju; Hao Ling (Chemosphere, 2023)

Systematic framework for sustainable urban road alignment planning - Feng Jiang; Ling Ma; Tim Broyd; Junda Li; Jing Jia; Hanbin Luo (Transportation Research Part D: Transport and Environment, 2023)

Removal of Cd2+, Pb2+ and Ni2+ from water by adsorption onto magnetic composites prepared using humic acid from waste biomass - Jiasheng Zhang; Xiaolong Li; Hang Xu; Wei Zhang; Xunlin Feng; Yidi Yao; Yanli Ma; Ling Su; Shixue Ren; Shujun Li (Journal of Cleaner Production, 2023)

Forecasting residential electricity consumption using the novel hybrid model - Guo-Feng Fan; Ya Zheng; Wen-Jing Gao; Li-Ling Peng; Yi-Hsuan Yeh; Wei-Chiang Hong (Energy and Buildings, 2023)

Anaerobic-aerobic treatment of high-strength and recalcitrant textile dyeing effluents - Hai-Yong Yao; Hui Guo; Feng Shen; Ting Li; De-Yang Show; Ming Ling; Yue-Gen Yan; Kuan-Yeow Show; Duu-Jong Lee (Bioresource Technology, 2023)

Characteristics and source apportionment of water-soluble inorganic ions in atmospheric particles in Lvliang, China - Tian Liu; Ling Mu; Xiaofan Li; Yangyong Li; Ziye Liu; Xin Jiang; Chuanyang Feng; Lirong Zheng (Environmental Geochemistry and Health, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Calcium-dependent activation of CPK12 facilitates its cytoplasm-to-nucleus translocation to potentiate plant hypoxia sensing by phosphorylating ERF-VII transcription factors - Biao Fan; Ke Liao; Lin-Na Wang; Li-Li Shi; Yi Zhang; Ling-Jing Xu; Ying Zhou; Jian-Feng Li; Yue-Qin Chen; Qin-Fang Chen; Shi Xiao (Molecular Plant, 2023)

Effects of drying methods on bioactive components of Ganoderma lucidum fermented whole wheat in products & in vitro digestive model - Yang Li; Fengying Gu; Xin Guo; Qiaozhen Zhang; Runrun Hu; Ling Qin; Qiang Wang; Feng Wang (Food Research International, 2023)

Optimization and mechanism of phosphorus removal in plant-biofilm oxidation ditches: Plant uptake, iron plaque adsorption, and rhizosphere regulation - Wen Liu; Feng-Juan Yang; Yong-Ling Zhou; Yi-Yong Li; Hui Liu; Dan A (Ecological Engineering, 2023)

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Conversion of swine manure into biochar for soil amendment: Efficacy and underlying mechanism of dissipating antibiotic resistance genes - Yan He; Xin Zhao; Siman Zhu; Long Yuan; Xinyi Li; Zhihan Feng; Xuan Yang; Ling Luo; Yinlong Xiao; Yan Liu; Lilin Wang; Ouping Deng (Science of The Total Environment, 2023)

Reactivation of NiSO4/ZnO-Al2O3-SiO2 adsorbent for reactive adsorption desulfurization - Lan Li; Feng Ju; Hao Ling (Fuel, 2023)

Prediction of vitrinite reflectance of shale oil reservoirs using nuclear magnetic resonance and conventional log data - Cheng Feng; Ziyan Feng; Rui Mao; Guanglei Li; Yuntao Zhong; Kegang Ling (Fuel, 2023)

Nickel exposure induces gut microbiome disorder and serum uric acid elevation - Jinfeng Yang; Pengya Feng; Zhenmin Ling; Aman Khan; Xing Wang; Yanli Chen; Gohar Ali; Yitian Fang; El-Sayed Salama; Ximei Wang; Pu Liu; Xiangkai Li (Environmental Pollution, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Emestrin-type thiodiketopiperazines from Aspergillus nidulans SD-531, a fungus obtained from the deep-sea sediment of cold seep in the South China Sea - Feng-Yi Lv; Attila Mándi; Xiao-Ming Li; Lu-Ping Chi; Xin Li; Bin-Gui Wang; Tibor Kurtán; Ling-Hong Meng (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Timing and seismic origin of the historic Luanshibao rock avalanche in the Maoyaba basin, SE Tibetan Plateau: New evidence from 10Be exposure-ages - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding; Guoqing Zhao (Quaternary Geochronology, 2023)

Dual polymer electrochromic sunglasses with black to anti-blue-ray conversion based on new anti-blue-ray transparent polymer - Haichang Fu; Yixiao Tang; Feng Zhan; Ling Zhang; Wang Zhan; Yujie Dong; Weijun Li; Cheng Zhang (Chemical Engineering Journal, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Biological effects on the migration and transformation of microplastics in the marine environment - Songyao Fan; Zezheng Yan; Ling Qiao; Feng Gui; Tiejun Li; Qiao Yang; Xiaoling Zhang; Chengzhe Ren (Marine Environmental Research, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Identification of structural variations related to drought tolerance in wheat (Triticum aestivum L.) - Jiajia Zhao; Xiaohua Li; Ling Qiao; Xingwei Zheng; Bangbang Wu; Meijun Guo; Meichen Feng; Zengjun Qi; Wude Yang; Jun Zheng (Theoretical and Applied Genetics, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Where does the runoff come from in dry season in the source region of the Yangtze River? - Li Zongjie; Liu Mengqing; Li Zongxing; Feng Qi; Song Ling-Ling; Xu Bin; Liu Xiaoying; Gui Juan (Agricultural and Forest Meteorology, 2023)

The galU gene is required for in vivo survival of pseudomonas plecoglossicida in large yellow croaker ( Larimichthys crocea ) - Feng‐Ling Shu; Li‐Yun Jin; Hao Liu; Zhen Tao; Fei Yin; Jia‐Song Xie; Su‐Ming Zhou (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida is an important pathogenic bacterium in aquaculture that causes visceral granulomas in large yellow croaker ( Larimichthys crocea ). Uridine diphosphate glucose phosphorylase encoded by galU plays a key role in biosynthesis of the bacterial envelope, particularly lipopolysaccharide and the capsule. In this study, we inactivated the galU gene in the P. plecoglossicida isolate XSDHY‐P. The galU mutant strain showed impaired growth in the early exponential stage and lacked the O polysaccharide side chain in lipopolysaccharide, but almost no defect in biofilm formation was detected. The galU mutant strain also exhibited significantly more sensitivity to the bactericidal action of normal fish serum mediated by the complement system compared to the wild‐type strain. In a cell model originating from the head kidney of large yellow croaker, the galU mutant strain showed lower capacities of adhesion, invasion, and intracellular survival compared to the wild‐type strain. In addition, the deficiency of the galU mutant drastically decreased bacterial loads in tissues and attenuated P. plecoglossicida virulence in fish. These results suggest that the galU gene of P. plecoglossicida is required for in vivo survival in large yellow croaker.

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Characterizing formation mechanisms of secondary aerosols on black carbon in a megacity in South China - Jing Wei; Ying-Bo Niu; Meng-Xue Tang; Yan Peng; Li-Ming Cao; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

Catalytic capacity evolution of montmorillonite in in-situ combustion of heavy oil - Xianghui Zhang; Junjie Wang; Ling Wang; Zhongquan Li; Wei Hu; Yanqiu Dai; Yuanyu Kou; Shengjun Lei; Qian Li; Wen Zhang; Hongkui Li; Ruyan Wang; et al. (Fuel, 2023)

6His-tatritin promotes antimicrobial defense via regulating immune ability and intestinal microbial community in grass carp (Ctenopharyngodon idella) - Wei-Feng Wang; Chu-Xing Cheng; Hong Liu; Xiu-Li Chen; Huan-Ling Wang (Fish & Shellfish Immunology, 2023)

Unveiling the origin of high-efficiency charge transport effect of C3N5/C3N4 homojunction for activating peroxymonosulfate to degrade atrazine under visible light - Yaocheng Deng; Ling Li; Hao Zeng; Rongdi Tang; Zhanpeng Zhou; Yuchen Sun; Chengyang Feng; Daoxin Gong; Jiajia Wang; Ying Huang (Chemical Engineering Journal, 2023)

Ultrahigh sensitive, sensing-actuating integrated, and multi-functional intelligent skin based on electromechanical-hydraulic coupling - Xiao Lei; Li-Jun Ma; Si-Nan Yu; Tian-Ling Ren; Shi-Feng Li; Jun Yuan; Lei Ye; Xu Yu; Feng Liu (Chemical Engineering Journal, 2023)

Enhanced elimination of Cr(VI) from aqueous media by polyethyleneimine modified corn straw biochar supported sulfide nanoscale zero valent iron: Performance and mechanism - Haoran Tian; Chao Huang; Ping Wang; Jie Wei; Xinyan Li; Ruimei Zhang; Dingxun Ling; Chongling Feng; Hao Liu; Mengxin Wang; Zhiming Liu (Bioresource Technology, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

Thin-walled vesicular Triazole-CN-PDI with electronic n→π* excitation and directional movement for enhanced atrazine photodegradation - Rongdi Tang; Hao Zeng; Daoxin Gong; Yaocheng Deng; Sheng Xiong; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chengyang Feng; Lin Tang (Chemical Engineering Journal, 2023)

Insights into the dual Z-scheme and piezoelectricity co-driven photocatalyst for ultra-speed degradation of nitenpyram - Sheng Xiong; Hao Zeng; Yaocheng Deng; Chengyang Feng; Rongdi Tang; Zhanpeng Zhou; Ling Li; Jiajia Wang; Daoxin Gong (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Role of melatonin receptor 1B gene polymorphism and its effect on the regulation of glucose transport in gestational diabetes mellitus - Lijie Wei; Yi Jiang; Peng Gao; Jingyi Zhang; Xuan Zhou; Shenglan Zhu; Yuting Chen; Huiting Zhang; Yuanyuan Du; Chenyun Fang; Jiaqi Li; Xuan Gao; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

CAF-derived midkine promotes EMT and cisplatin resistance by upregulating lncRNA ST7-AS1 in gastric cancer - Ke-Da Yang; Ying Wang; Fan Zhang; Qing-Ling Li; Bai-Hua Luo; De-Yun Feng; Zhi-Jun Zeng (Molecular and Cellular Biochemistry, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

UBR5 promotes migration and invasion of glioma cells by regulating the ECRG4/NF-κB pathway - Qiang Wu; Ling Liu; Yan Feng; Liqun Wang; Xin Liu; Yanan Li (Journal of Biosciences, 2022)

β-Cyclodextrin-Grafted Chitosan Enhances Intestinal Drug Absorption and Its Preliminary Mechanism Exploration - Linghui Zou; Zhongbin Zhang; Jinqing Chen; Xu Yang; Yuyang Li; Jing Tang; Xiaolu Du; Ling Tang; Dan Liang; Xiaoyong Zhu; Jianfang Feng; Wenya Ding (AAPS PharmSciTech, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Exogenous Ca2+ Associated with Melatonin Alleviates Drought-Induced Damage in the Woody Tree Dalbergia odorifera - El-Hadji Malick Cisse; Li-Jia Zhang; Yu-Jin Pu; Ling-Feng Miao; Da-Dong Li; Juan Zhang; Fan Yang (Journal of Plant Growth Regulation, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Efficient de novo assembly and modification of large DNA fragments - Shuangying Jiang; Yuanwei Tang; Liang Xiang; Xinlu Zhu; Zelin Cai; Ling Li; Yingxi Chen; Peishuang Chen; Yuge Feng; Xin Lin; Guoqiang Li; Jafar Sharif; et al. (Science China Life Sciences, 2022)

Correction to: Short‑term effects of gaseous air pollutants on outpatient visits for respiratory diseases: a case‑crossover study in Baotou, China - Hao‑Yu Gao; Xiao‑Ling Liu; Ya‑Ke Lu; Yu‑Hong Liu; Li‑Kun Hu; Yan‑Ling Li; Xiao‑Dong Feng; Yu‑Xiang Yan (Environmental Science and Pollution Research, 2022)

Short-term effects of gaseous air pollutants on outpatient visits for respiratory diseases: a case-crossover study in Baotou, China - Hao-Yu Gao; Xiao-Ling Liu; Ya-Ke Lu; Yu-Hong Liu; Li-Kun Hu; Yan-Ling Li; Xiao-Dong Feng; Yu-Xiang Yan (Environmental Science and Pollution Research, 2022)

Isolation and characterization of AaZFP1, a C2H2 zinc finger protein that regulates the AaIPPI1 gene involved in artemisinin biosynthesis in Artemisia annua - Yin-ai Deng; Li Li; Qian Peng; Ling-fang Feng; Jin-fen Yang; Ruo-ting Zhan; Dong-ming Ma (Planta, 2022)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Quinoline, with the active site of 8‐hydroxyl, efficiently inhibits Micropterus salmoides rhabdovirus (MSRV) infection in vitro and in vivo - Bo‐Yang Li; Fei Yang; Zhong‐Yu Zhang; Yu‐Feng Shen; Tao Wang; Liang Zhao; Jia‐Cheng Qin; Fei Ling; Gao‐Xue Wang (Journal of Fish Diseases, 2022)
Micropterus salmoides rhabdovirus (MSRV) is an significant pathogen that causes high mortality and related economic losses in bass aquaculture. There is no effective or approved therapy to date. In this study, we evaluated the anti‐MSRV effects of 22 quinoline derivatives in grass carp ovary (GCO) cells. Among these compounds, 8‐hydroxyquinoline exhibited valid inhibition in decreasing MSRV nucleoprotein gene expression levels of 99.3% with a half‐maximal inhibitory concentrations (IC 50 ) value of 4.66 μM at 48 h. Moreover, 8‐hydroxyquinoline significantly enhanced a protective effect in GCO cells by reducing the cytopathic effect (CPE). By comparing the anti‐MSRV activity of 22 quinoline derivatives, we found that 8‐hydroxyquinoline possessed the efficient active site of 8‐hydroxyl and inhibited MSRV infection in vitro. For in vivo studies, 8‐hydroxyquinoline via intraperitoneal injection exhibited an antiviral effect in MSRV‐infected largemouth bass by substantially enhancing the survival rate by 15.0%. Importantly, the viral loads in the infected largemouth bass notably reduced in the spleen on the third days post‐infection. Overall, 8‐hydroxyquinoline was considered to be an efficient agent against MSRV in aquaculture.

Hypoxia Stress Induces Tissue Damage, Immune Defense, and Oxygen Transport Change in Gill of Silver Carp (Hypophthalmichthys molitrix): Evaluation on Hypoxia by Using Transcriptomics - Xiaohui Li; Chen Ling; Qiaoxin Wang; Cui Feng; Xiangzhong Luo; Hang Sha; Guoyu He; Guiwei Zou; Hongwei Liang (Frontiers in Marine Science, 2022)
The silver carp ( Hypophthalmichthys molitrix ) is an economically, as well as environmentally, important fish that harbors low environmental hypoxia tolerance and frequently contributes to a loss of aquaculture productivity. The gill is the first tissue attacked by hypoxia; however, the response of the gills of H. molitrix to hypoxia stress at the tissue, cellular, and molecular levels has not been clearly established. The influence of hypoxia on histological features along with gene expression in silver carp gills were explored in this research. The hematoxylin and eosin-stained sections and electron microscopy examinations of gills indicated that the gill lamellae were seriously twisted, gill filaments were dehisced, and the swelling and shedding of epithelial cell layer in the gill tissue were intensified along with the degree of hypoxia. In the hypoxia, semi-asphyxia, and asphyxia groups, the gill transcriptomic assessment of shifts in key genes, as well as modulatory networks in response to hypoxic conditions revealed 587, 725, and 748 differentially expressed genes, respectively. These genes are abundant in immune response signaling cascades (e.g., complement and coagulation cascades, Nucleotide-binding and oligomerization domain (NOD)-like receptor signaling cascade, and differentiation of Th1 along with Th2 cells) and oxygen transport [e.g., MAPK, PI3K-Akt, and hypoxia-inducible factor 1 (HIF-1) signaling cascades]. Genes linked to immune response (e.g., c2 , c3 , c6 , klf4 , cxcr4 , cd45 , and cd40 ) and oxygen transport (e.g., egln1 , egln3 , epo , ldh , and vegfa ) were additionally identified. According to our findings, the silver carp may be using “HIF-1” to obtain additional oxygen during hypoxia. These findings illustrate that hypoxia stress might damage gill tissue, trigger an immunological response, and activate HIF-1 signaling to increase oxygen availability under hypoxic situations. The findings of this work will help scientists better understand the molecular mechanisms driving hypoxia responses in hypoxia-sensitive fish and speed up the development of hypoxia-resistant varieties.

Environmental drivers of soil microbial activity and diversity along an elevational gradient - Si-li Peng; Zhi-wei Ge; Gang-cai Liu; Ling-feng Mao (Journal of Mountain Science, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Maternal embryonic leucine zipper kinase serves as a potential prognostic marker and leads to sorafenib chemoresistance modified by miR-142-5p in hepatocellular carcinoma - Hualei Li; Ling Gai; Zhimei Wu; Feng Li (Molecular Biology Reports, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Functional Mechanism of Antimicrobial Peptide Bomidin and Its Safety for Macrobrachium rosenbergii - Miao Zhang; Youli Yu; Lele Lian; Wanjun Li; Jianluan Ren; Ying Liang; Feng Xue; Fang Tang; Xiaohua Zhu; Jianqun Ling; Jianjun Dai (Probiotics and Antimicrobial Proteins, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Two new iridoid glycosides from the fruit of Gardenia jasminoides - Hai-Bo Li; Jin-Feng Ma; Yu-Dan Mei; Ling-Xian Liu; Ze-yu Cao; Dan-Feng Shi; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

β-Catenin Deletion in Regional Neural Progenitors Leads to Congenital Hydrocephalus in Mice - Lin Ma; Yanhua Du; Xiangjie Xu; Hexi Feng; Yi Hui; Nan Li; Guanyu Jiang; Xiaoqing Zhang; Xiaocui Li; Ling Liu (Neuroscience Bulletin, 2022)

Effects of ecological projects on vegetation in the Three Gorges Area of Chongqing, China - Feng Li; Wen-zuo Zhou; Zhou-ling Shao; Xin-yao Zhou (Journal of Mountain Science, 2022)

Three new cycloart-7-ene triterpenoid glycosides from Cimicifuga dahurica and their anti-inflammatory effects - Qian-Qian Pang; Yu-Dan Mei; Yuan-Chu Zhang; Ling-Xian Liu; Dan-Feng Shi; Da-Bo Pan; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2021)

A new nitrogen-containing iridoid glycoside from lonicera macranthoides - Yu-Dan Mei; Hai-Bo Li; Ling-Xian Liu; Dan-feng Shi; Da-bo Pan; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2021)

Coupling exogenous melatonin with Ca2+ alleviated chilling stress in Dalbergia odorifera T. Chen - Yu-Jin Pu; El Hadji Malick Cisse; Li-Jia Zhang; Ling-Feng Miao; Mohsin Nawaz; Fan Yang (Trees, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Two new norsesquiterpenoids with estrogenic activity from the stems and leaves of Dioscorea oppositifolia L - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Bei-Bei Zhang; Yan-Ling Liu; Meng-Na Wang; Yan-Li Zhang; Wei-Sheng Feng; Xiao-Ke Zheng (Natural Product Research, 2021)

Development of nuclear and chloroplast polymorphic microsatellites for Crossostephium chinense (Asteraceae) - Luxian Liu; Shook Ling Low; Shota Sakaguchi; Yu Feng; Binjie Ge; Kamil Konowalik; Pan Li (Molecular Biology Reports, 2021)

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1) - Ming Li; Ling Xue; Weibin Xu; Pingping Liu; Feng Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The apoptosis of GCs was facilitated by NE. Wilms tumor 1 (WT1) was found to be significantly downregulated in GCs after NE treatment, and overexpression of WT1 repressed apoptosis in rat GCs induced by NE. rno-miR-128-3p was found to be significantly enhanced by NE in GCs, and inhibition of rno-miR-128-3p repressed apoptosis in rat GCs induced by NE. Mechanistically, rno-miR-128-3p interacted with WT1 and repressed its expression. In summary, inhibition of rno-miR-128-3p may enhance WT1 expression, and then repress NE-induced apoptosis in rat GCs. Our research may provide a new insight for the improvement of ovarian follicular development.

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Characterization of Organic Aerosol at a Rural Site in the North China Plain Region: Sources, Volatility and Organonitrates - Qiao Zhu; Li-Ming Cao; Meng-Xue Tang; Xiao-Feng Huang; Eri Saikawa; Ling-Yan He (Advances in Atmospheric Sciences, 2021)

Chelerythrine Ameliorates Pulmonary Fibrosis via Activating the Nrf2/ARE Signaling Pathway - Ling Peng; Li Wen; Qingfeng Shi; Feng Gao; Bin Huang; Changming Wang (Cell Biochemistry and Biophysics, 2021)

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Activity evolution of landslides and debris flows after the Wenchuan earthquake in the Qipan catchment, Southwest China - Qing-yun Shi; Chuan Tang; Ling-feng Gong; Ming Chen; Ning Li; Wei Zhou; Jiang Xiong; Hai Tang; Xiao-di Wang; Ming-wei Li (Journal of Mountain Science, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

Siccirubricoccus phaeus sp. nov., isolated from oil reservoir water and emended description of the genus Siccirubricoccus - Fang-Ling Li; Ya-Xi Zhang; Ya-Kun Zhang; Wen-Feng Chen; Wen-Jun Li; Lei Wang (Antonie van Leeuwenhoek, 2021)

MSC-AS1 knockdown inhibits cell growth and temozolomide resistance by regulating miR-373-3p/CPEB4 axis in glioma through PI3K/Akt pathway - Chong Li; Shiyu Feng; Ling Chen (Molecular and Cellular Biochemistry, 2021)
Long non-coding RNAs (lncRNAs) have been widely reported to regulate the development and chemoresistance of a variety of tumors. Temozolomide (TMZ) is a first-line chemotherapy for treatment of glioma. However, the effect and the regulatory mechanism of lncRNA MSC-AS1 (MSC-AS1) in TMZ-resistant glioma remain unrevealed. Levels of MSC-AS1, microRNA-373-3p (miR-373-3p), and cytoplasmic polyadenylation element binding protein 4 (CPEB4) were determined by quantitative real-time polymerase chain reaction (qRT-PCR). All protein expression was detected by western blot. Cell viability and the half maximal inhibitory concentration (IC 50 ) value of TMZ was assessed by cell counting kit-8 (CCK-8) assay. Cell cloning ability and apoptosis were examined by colony formation and flow cytometry assays, respectively. Dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were performed to verify the correlation between miR-373-3p and MSC-AS1 or CPEB4. The xenograft models were established to determine the effect of MSC-AS1 in vivo. MSC-AS1 was up-regulated in TMZ-resistant glioma tissues and cells, and glioma patients with high MSC-AS1 expression tend to have lower overall survival rate. MSC-AS1 suppression reduced the IC 50 value of TMZ and proliferation, promoted apoptosis and TMZ sensitivity, and affected PI3K/Akt pathway in TMZ-resistant glioma cells. MSC-AS1 acted as miR-373-3p sponge, and miR-373-3p directly targeted CPEB4. Silencing miR-373-3p reversed the promoting effect of MSC-AS1 or CPEB4 knockdown on TMZ sensitivity. Furthermore, MSC-AS1 knockdown inhibited TMZ-resistant glioma growth in vivo by regulating miR-373-3p/CPEB4 axis through PI3K/Akt pathway. Collectively, MSC-AS1 knockdown suppressed cell growth and the chemoresistance of glioma cells to TMZ by regulating miR-373-3p/CPEB4 axis in vitro and in vivo through activating PI3K/Akt pathway.

Post-mining failure characteristics of rock surrounding coal seam roadway and evaluation of rock integrity: a case study - Qiang-ling Yao; Qiang Xu; Jiang-feng Liu; Liu Zhu; Dong-wei Li; Chuan-jin Tang (Bulletin of Engineering Geology and the Environment, 2021)

Application of 1H-NMR combined with qRT-PCR technology in the exploration of rosmarinic acid biosynthesis in hair roots of Salvia miltiorrhiza Bunge and Salvia castanea f. tomentosa Stib - Zhuoni Hou; Yuanyuan Li; Feng Su; Jipeng Chen; Xiaodan Zhang; Ling Xu; Dongfeng Yang; Zongsuo Liang (Planta, 2021)
Main conclusion Methyl jasmonate promotes the synthesis of rosmarinic acid in Salvia miltiorrhiza Bunge and Salvia castanea f. tomentos a Stib, and it promotes the latter more strongly. Abstract Salvia miltiorrhiza Bunge (SMB) is a traditional Chinese medicinal material, its water-soluble phenolic acid component rosmarinic acid has very important medicinal value. Salvia castanea f . tomentosa Stib (SCT) mainly distributed in Nyingchi, Tibet. Its pharmacological effects are similar to SMB, but its rosmarinic acid is significantly higher than the former. Methyl jasmonate (MJ) as an inducer can induce the synthesis of phenolic acids in SMB and SCT. However, the role of MJ on rosmarinic acid in SMB is controversial. Therefore, this study used SMB and SCT hair root as an experimental material and MJ as a variable. On one hand, exploring the controversial reports in SMB; on the other hand, comparing the differences in the mechanism of action of MJ on the phenolic acids in SMB and SCT. The content of related metabolites and the expression of key genes in the synthesis pathway of rosmarinic acid was analyzed by 1 H-NMR combined with qRT-PCR technology. Our research has reached the following conclusions: first of all, MJ promotes the accumulation of rosmarinic acid and related phenolic acids in the metabolic pathways of SMB and SCT. After MJ treatment, the content of related components and gene expression are increased. Second, compared to SMB, SCT has a stronger response to MJ. It is speculated that the different responses of secondary metabolism-related genes to MJ may lead to different metabolic responses of salvianolic acid between the two.

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

Numerical simulation of the moisture migration of unsaturated clay embankments in southern China considering stress state - Junhui Zhang; Feng Li; Ling Zeng; Junhui Peng; Jue Li (Bulletin of Engineering Geology and the Environment, 2021)

Silencing of DsbA-L gene impairs the PPARγ agonist function of improving insulin resistance in a high-glucose cell model - Xuan Zhou; Jia-qi Li; Li-jie Wei; Meng-zhou He; Jing Jia; Jing-yi Zhang; Shao-shuai Wang; Ling Feng (Journal of Zhejiang University-SCIENCE B, 2020)

Association of ADH7 Gene Polymorphism with Schizophrenia in the Han Population of Northern China: a Case-Control Study - Kuo Zeng; Ya Li; Meng Gao; Yong-ping Liu; Feng-ling Xu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

Removal of antipyrine through two-dimensional and three-dimensional electrolysis: comparison, modification, and improvement - Pengxiao Liu; Xu Wang; Jing Lu; Ying Li; Bin Hou; Ling Feng (Environmental Science and Pollution Research, 2020)

An Experimental Study of Effect of High Temperature on the Permeability Evolution and Failure Response of Granite Under Triaxial Compression - Sheng-Qi Yang; Wen-Ling Tian; Derek Elsworth; Jian-Guo Wang; Li-Feng Fan (Rock Mechanics and Rock Engineering, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Combined addition of chemical and organic amendments enhances plant resistance to aboveground herbivores through increasing microbial abundance and diversity - Linhui Jiang; Michael Bonkowski; Ling Luo; Paul Kardol; Yu Zhang; Xiaoyun Chen; Daming Li; Zhenggao Xiao; Feng Hu; Manqiang Liu (Biology and Fertility of Soils, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Pentamidine sensitizes FDA-approved non-antibiotics for the inhibition of multidrug-resistant Gram-negative pathogens - Chenxuan Wu; Ling Xia; Wei Huang; Yangfan Xu; Yuanxin Gu; Chang Liu; Luting Ji; Wenyao Li; Yandong Wu; Kai Zhou; Xinxin Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

A potentially important resource: endophytic yeasts - Lijun Ling; Yixin Tu; Wenxia Ma; Shenglai Feng; Caiyun Yang; Yunhua Zhao; Nan Wang; Zibin Li; Lu Lu; Ji Zhang (World Journal of Microbiology and Biotechnology, 2020)

Variation of biogeochemical cycle of riverine dissolved inorganic carbon and silicon with the cascade damming - Haojun Deng; Zhen Tao; Quanzhou Gao; Ling Yao; Yong Feng; Yinhua Li; Jian Ding; Zhengang Wang; Xiaoxi Lyu; Peng Xu (Environmental Science and Pollution Research, 2020)

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Correction to: Intra-host diversity of hepatitis B virus during mother-to-child transmission: the X gene may play a key role in virus survival in children after transmission - Yanjie Li; Chenguang Shen; Liuqing Yang; Yang Yang; Miao Wang; Shanqin Li; Feng Chen; Min Yang; Ling Peng; Jinmin Ma; Zhongping Duan; Liqiang Li; et al. (Archives of Virology, 2020)

Genome-Wide Analysis of LAZ1 Gene Family from Maize - Bing Liang Liu; Hao Qiang Yu; Qian Wen; Feng Ling Fu; Wan Chen Li (Journal of Plant Growth Regulation, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Intra-host diversity of hepatitis B virus during mother-to-child transmission: the X gene may play a key role in virus survival in children after transmission - Yanjie Li; Chenguang Shen; Liuqing Yang; Yang Yang; Miao Wang; Shanqin Li; Feng Chen; Min Yang; Ling Peng; Jinmin Ma; Zhongping Duan; Liqiang Li; et al. (Archives of Virology, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Retraction Note to: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2020)

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Function of NHX-type transporters in improving rice tolerance to aluminum stress and soil acidity - Weihong Li; Jia Du; Huimin Feng; Qi Wu; Guohua Xu; Sergey Shabala; Ling Yu (Planta, 2020)

Not all Neoproterozoic iron formations are glaciogenic: Sturtian-aged non-Rapitan exhalative iron formations from the Arabian–Nubian Shield - Yasser Abd El-Rahman; Jens Gutzmer; Xian-Hua Li; Thomas Seifert; Chao-Feng Li; Xiao-Xiao Ling; Jiao Li (Mineralium Deposita, 2020)

Effects of amygdalin on type II collagen-induced arthritis in rats - Demei Luo; Qian Wang; Yan Meng; Ling Cao; Ning Feng; Wenjing Du; Huijun Li; Xunan Dong; Xiumin Ma; Li Luo (Biologia, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

One-Pot Hydrothermal Synthesis of Carbon Quantum Dots with Excellent Photoluminescent Properties and Catalytic Activity from Coke Powders - Ling Ding; Kuntao Huang; Shiqian Li; Jin Zhou; Huan He; Zeze Peng; Sobhan Chatterjee; Feng Liang (Journal of Fluorescence, 2020)

Multiplexed Non-barcoded Long-Read Sequencing and Assembling Genomes of Bacillus Strains in Error-Free Simulations - Jiating Qian; Qiao Meng; Yifan Feng; Xuanxuan Mao; Yayue Ling; Jie Li (Current Microbiology, 2020)

Cytological, genetic, and proteomic analysis of a sesame (Sesamum indicum L.) mutant Siyl-1 with yellow–green leaf color - Tong-Mei Gao; Shuang-Ling Wei; Jing Chen; Yin Wu; Feng Li; Li-Bin Wei; Chun Li; Yan-Juan Zeng; Yuan Tian; Dong-Yong Wang; Hai-Yang Zhang (Genes & Genomics, 2020)
Background Both photosynthetic pigments and chloroplasts in plant leaf cells play an important role in deciding on the photosynthetic capacity and efficiency in plants. Systematical investigating the regulatory mechanism of chloroplast development and chlorophyll (Chl) content variation is necessary for clarifying the photosynthesis mechanism for crops. Objective This study aims to explore the critical regulatory mechanism of leaf color mutation in a yellow–green leaf sesame mutant Siyl - 1 . Methods We performed the genetic analysis of the yellow-green leaf color mutation using the F 2 population of the mutant Siyl - 1 . We compared the morphological structure of the chloroplasts, chlorophyll content of the three genotypes of the mutant F 2 progeny. We performed the two-dimensional gel electrophoresis (2-DE) and compared the protein expression variation between the mutant progeny and the wild type. Results Genetic analysis indicated that there were 3 phenotypes of the F 2 population of the mutant Siyl - 1 , i.e., YY type with light-yellow leaf color (lethal); Yy type with yellow-green leaf color, and yy type with normal green leaf color. The yellow-green mutation was controlled by an incompletely dominant nuclear gene, Siyl - 1 . Compared with the wild genotype, the chloroplast number and the morphological structure in YY and Yy mutant lines varied evidently. The chlorophyll content also significantly decreased ( P < 0.05 ). The 2-DE comparison showed that there were 98 differentially expressed proteins (DEPs) among YY, Yy, and yy lines. All the 98 DEPs were classified into 5 functional groups. Of which 82.7% DEPs proteins belonged to the photosynthesis and energy metabolism group. Conclusion The results revealed the genetic character of yellow-green leaf color mutant Siyl - 1 . 98 DEPs were found in YY and Yy mutant compared with the wild genotype. The regulation pathway related with the yellow leaf trait mutation in sesame was analyzed for the first time. The findings supplied the basic theoretical and gene basis for leaf color and chloroplast development mechanism in sesame.

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Permanent disappearance and seasonal fluctuation of urban lake area in Wuhan, China monitored with long time series remotely sensed images from 1987 to 2016 - Lingfei Shi; Feng Ling; Giles M Foody; Cheng Chen; Shiming Fang; Xiaodong Li; Yihang Zhang; Yun Du (International Journal of Remote Sensing, 2019)

Two highly oxygenated Ergosterols from cultures of the Basidiomycete Conocybe siliginea - Chao-Jun Pu; Yue-Ling Peng; Zheng-Hui Li; Juan He; Rong Huang; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

RETRACTED ARTICLE: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens - Min-jie Zhao; Hai-ying Cai; Meng-yun Liu; Ling-li Deng; Yang Li; Hui Zhang; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Identification of Novel Endophytic Yeast Strains from Tangerine Peel - Lijun Ling; Zibin Li; Zhenglong Jiao; Xi Zhang; Wenxia Ma; Juanjuan Feng; Ji Zhang; Lu Lu (Current Microbiology, 2019)

Genetic diversity of ten black walnut (Juglans nigra L.) cultivars and construction of a mapping population - S. Jacob Schneider; Anna Y. Hwang; Sadie D. Land; Li-Ling Chen; Andrew L. Thomas; Chin-Feng Hwang (Tree Genetics & Genomes, 2019)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

Development of a reverse genetics system for Japanese encephalitis virus strain SA14-14-2 - Guohua Li; Hongli Jin; Xin Nie; Yongkun Zhao; Na Feng; Zongxi Cao; Shuyi Tan; Bo Zhang; Weiwei Gai; Feihu Yan; Ling Li; Ying Zhang; et al. (Virus Genes, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Geodynamic transition from subduction to extension: evidence from the geochronology and geochemistry of granitoids in the Sangsang area, southern Lhasa Terrane, Tibet - Feng Huang; Mingjian Li; Jifeng Xu; Yunchuan Zeng; Jianlin Chen; Baodi Wang; Hongxia Yu; Ling Chen; Peipei Zhao; Zhao Zhang (International Journal of Earth Sciences, 2019)

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

A novel phage from periodontal pockets associated with chronic periodontitis - Yu Zhang; Tong-Ling Shan; Fei Li; Tian Yu; Xi Chen; Xu-Tao Deng; Eric Delwart; Xi-Ping Feng (Virus Genes, 2019)

Genome-wide identification, phylogeny, and expression analysis of Sec14-like PITP gene family in sugarcane - Mao Hua-ying; Wang Wen-ju; Su Wei-hua; Su Ya-chun; Liu Feng; Li Cong-na; Wang Ling; Zhang Xu; Xu Li-ping; Que You-xiong (Plant Cell Reports, 2019)

Protective effect of dihydromyricetin on hyperthermia-induced apoptosis in human myelomonocytic lymphoma cells - Qian-Wen Feng; Zheng-Guo Cui; Yu-Jie Jin; Lu Sun; Meng-Ling Li; Shahbaz Ahmad Zakki; De-Jun Zhou; Hidekuni Inadera (Apoptosis, 2019)

Sequestration of Mn into the cell wall contributes to Mn tolerance in sugarcane (Saccharum officinarum L.) - Shu Yang; Ke Yi; Min Min Chang; Gui Zhi Ling; Zun Kang Zhao; Xiao Feng Li (Plant and Soil, 2019)

Limited potential of harvest index improvement to reduce methane emissions from rice paddies - Yu Jiang; Haoyu Qian; Ling Wang; Jinfei Feng; Shan Huang; Bruce A. Hungate; Chris van Kessel; William R. Horwath; Xingyue Zhang; Xiaobo Qin; Yue Li; Xiaomin Feng; et al. (Global Change Biology, 2019)
Rice is a staple food for nearly half of the world's population, but rice paddies constitute a major source of anthropogenic CH 4 emissions. Root exudates from growing rice plants are an important substrate for methane‐producing microorganisms. Therefore, breeding efforts optimizing rice plant photosynthate allocation to grains, i.e., increasing harvest index (HI), are widely expected to reduce CH 4 emissions with higher yield. Here we show, by combining a series of experiments, meta‐analyses and an expert survey, that the potential of CH 4 mitigation from rice paddies through HI improvement is in fact small. Whereas HI improvement reduced CH 4 emissions under continuously flooded (CF) irrigation, it did not affect CH 4 emissions in systems with intermittent irrigation (II). We estimate that future plant breeding efforts aimed at HI improvement to the theoretical maximum value will reduce CH 4 emissions in CF systems by 4.4%. However, CF systems currently make up only a small fraction of the total rice growing area (i.e., 27% of the Chinese rice paddy area). Thus, to achieve substantial CH 4 mitigation from rice agriculture, alternative plant breeding strategies may be needed, along with alternative management.

Construction of a high-density linkage map and QTL detection of downy mildew resistance in Vitis aestivalis-derived ‘Norton’ - Surya Sapkota; Li-Ling Chen; Shanshan Yang; Katie E. Hyma; Lance Cadle-Davidson; Chin-Feng Hwang (Theoretical and Applied Genetics, 2019)

Effects of long-term coastal reclamation on suitable habitat and wintering population size of the endangered Red-crowned Crane, Grus japonensis - Ning Li; Zheng Wang; Lu Xia; Feng Yan; Ling-qian Xu; Ya-jun Qiao; Xin-hai Li; Shu-qing An; Shu-bo Fang (Hydrobiologia, 2019)

Urbanization effects on changes in the observed air temperatures during 1977–2014 in China - Yuanzheng Li; Lan Wang; Hongxuan Zhou; Guosong Zhao; Feng Ling; Xiaodong Li; Juan Qiu (International Journal of Climatology, 2019)
This study endeavoured to accurately estimate the effects of urbanization on changes in temperatures during 1977–2014 throughout China. To this end, we (a) classified the stations using improved standards, (b) homogenized the mean minimum (Tmin), mean maximum (Tmax), and mean temperature (Tm) data series, (c) identified regions with different temperature trends based on the modified methodology, and analysed the regional changes in the background rural temperatures, (d) explored the relationships between the temperature trend effects of urbanization and the three indices of the urbanization intensity, and (a) calculated the contribution from urbanization on the regional scale. The results indicated the following: (a) After homogenization, several adjustment amplitudes were larger than 1 °C, the maximum value of which reached 7.84 °C. (b) China was divided into six regions with different rural temperature trends. Rural temperatures significantly increased throughout China with annual Tmin, Tmax and Tm changing rates of 0.424, 0.339, and 0.352 °C/decade, respectively. Throughout all of China, the maximum rates for Tmax, Tmin, and Tm occurred during the spring and the minimum rates for Tmax and Tm occurred during the summer, while that for Tmin was slightly lower in the winter than during the summer. (c) Significant correlations did not always exist between the urbanization‐contributed temperature‐changing rates and the indices of urbanization intensity, and the correlation coefficients varied under different conditions. These values were both positive and negative. The changes in the areas of the built‐up regions constituted the best correlation factors. (d) The percentages of the contributions of urbanization to the mean annual Tmin, Tmax, and Tm were −0.08, 0.21, and −0.09%, respectively. These results are beneficial for understanding the effects of urbanization on regional or global climate change to some extent.

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

New podolactones from the seeds of Podocarpus nagi and their anti-inflammatory effect - Zhe-Ling Feng; Tian Zhang; Jing-Xin Liu; Xiu-Ping Chen; Li-She Gan; Yang Ye; Li-Gen Lin (Journal of Natural Medicines, 2018)

Autophagy‐related gene BbATG11 is indispensable for pexophagy and mitophagy, and contributes to stress response, conidiation and virulence in the insect mycopathogen Beauveria bassiana - Jin‐Li Ding; Yue‐Jin Peng; Xin‐Ling Chu; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2018)
Summary Autophagy is a conserved degradation system in eukaryotic cells that includes non‐selective and selective processes. Selective autophagy functions as a selective degradation mechanism for specific substrates in which autophagy‐related protein 11 (ATG11) acts as an essential scaffold protein. In B. bassiana , there is a unique ATG11 family protein, which is designated as BbATG11 . Disruption of BbATG11 resulted in significantly reduced conidial germination under starvation stress. The mutant Δ BbATG11 displayed enhanced sensitivity to oxidative stress and impaired asexual reproduction. The conidial yield was reduced by approximately 75%, and this defective phenotype could be repressed by increasing exogenous nutrients. The virulence of the Δ BbATG11 mutant strain was significantly impaired as indicated in topical and intra‐hemocoel injection bioassays, with a greater reduction in topical infection. Notably, BbATG11 was involved in pexophagy and mitophagy, but these two autophagic processes appeared in different fungal physiological aspects. Both pexophagy and mitophagy were associated with nutrient shift, starvation stress and growth in the host hemocoel, but only pexophagy appeared in both oxidation‐stressed cells and aerial mycelia. This study highlights that BbATG11 mediates pexophagy and mitophagy in B. bassiana and links selective autophagy to the fungal stress response, conidiation and virulence.

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

Anti-inflammatory and anti-angiogenic activities in vitro of eight diterpenes from Daphne genkwa based on hierarchical cluster and principal component analysis - Ling Wang; Xin-Yi Lan; Jun Ji; Chun-Feng Zhang; Fei Li; Chong-Zhi Wang; Chun-Su Yuan (Journal of Natural Medicines, 2018)

Low-dose diethylhexyl phthalate exposure does not impair the expressive patterns of epigenetics-related genes and DNA methylation of breast cancer-related genes in mouse mammary glands - Shun-Feng Cheng; Ling Li; Bo Li; Jing-Cai Liu; Fang-Nong Lai; Yong Zhao; Xi-Feng Zhang; Wei Shen; Lan Li (Molecular & Cellular Toxicology, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

ELMOD3, a novel causative gene, associated with human autosomal dominant nonsyndromic and progressive hearing loss - Wu Li; Jie Sun; Jie Ling; Jiada Li; Chufeng He; Yalan Liu; Hongsheng Chen; Meichao Men; Zhijie Niu; Yuyuan Deng; Meng Li; Taoxi Li; et al. (Human Genetics, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Temporal patterns and processes of genetic differentiation of the Brachionus calyciflorus (Rotifera) complex in a subtropical shallow lake - Ye Zhang; Ao Zhou; Yi-Long Xi; Qiang Sun; Le-Feng Ning; Ping Xie; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2018)

Spatiotemporal characteristics of hydrochemistry in Asian arid inland basin–a case study of Shiyang River Basin - Ling Yang; Guofeng Zhu; Peiji Shi; Jiafang Li; Yuanfeng Liu; Huali Tong; Pengfei Hu; Feng Liang; Hanxiong Pan; Huiwen Guo; Yu Zhang (Environmental Science and Pollution Research, 2018)

Clinical and molecular analysis of 6 Chinese patients with isoleucine metabolism defects: identification of 3 novel mutations in the HSD17B10 and ACAT1 gene - Ling Su; Xiuzhen Li; Ruizhu Lin; Huiying Sheng; Zhichun Feng; Li Liu (Metabolic Brain Disease, 2017)

Abnormal structure and functional connectivity of the anterior insula at pain-free periovulation is associated with perceived pain during menstruation - Wang-huan Dun; Jing Yang; Ling Yang; Dun Ding; Xue-ying Ma; Feng-Li Liang; Karen M. von Deneen; Shao-hui Ma; Xiao-ling Xu; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2017)

Detection of a new species of torque teno mini virus from the gingival epithelium of patients with periodontitis - Yu Zhang; Fei Li; Xi Chen; Tong-Ling Shan; Xu-Tao Deng; Eric Delwart; Xi-Ping Feng (Virus Genes, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Establishment of a somatic embryo regeneration system and expression analysis of somatic embryogenesis-related genes in Chinese chestnut (Castanea mollissima Blume) - Dan Lu; Wei Wei; Wan Zhou; Linda D. McGuigan; Fei-yang Ji; Xiao Li; Yu Xing; Qing Zhang; Ke-feng Fang; Qing-qin Cao; Ling Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Remote estimation of cyanobacterial blooms using the risky grade index (RGI) and coverage area index (CAI): a case study in the Three Gorges Reservoir, China - Botian Zhou; Mingsheng Shang; Guoyin Wang; Li Feng; Kun Shan; Xiangnan Liu; Ling Wu; Xuerui Zhang (Environmental Science and Pollution Research, 2017)

Cloning and Stress-Induced Expression Analysis of Calmodulin in the Antarctic Alga Chlamydomonas sp. ICE-L - Ying-ying He; Yi-bin Wang; Zhou Zheng; Fang-ming Liu; Mei-ling An; Xiao-dong He; Chang-feng Qu; Lu-lu Li; Jin-lai Miao (Current Microbiology, 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Safety, tolerability, pharmacokinetics and pharmacodynamics of dexlansoprazole injection in healthy Chinese subjects - Yue-Qi Li; Zheng-Yu Yan; Hong-Wen Zhang; Lu-Ning Sun; Hui-Wen Jiao; Mei-Feng Wang; Li-Yuan Yu; Lei Yu; Zi-Qing-Yun Yuan; Ling Meng; Yong-Qing Wang (European Journal of Clinical Pharmacology, 2017)

Altered modular organization of intrinsic brain functional networks in patients with Parkinson’s disease - Qing Ma; Biao Huang; Jinhui Wang; Carol Seger; Wanqun Yang; Changhong Li; Junjing Wang; Jieying Feng; Ling Weng; Wenjie Jiang; Ruiwang Huang (Brain Imaging and Behavior, 2017)

Effect of nitrogen additions on root morphology and chemistry in a subtropical bamboo forest - Guan-tao Chen; Li-hua Tu; Yong Peng; Hong-ling Hu; Ting-xing Hu; Zhen-feng Xu; Li Liu; Yi Tang (Plant and Soil, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Young Seedling Stripe1 encodes a chloroplast nucleoid-associated protein required for chloroplast development in rice seedlings - Kunneng Zhou; Yulong Ren; Feng Zhou; Ying Wang; Long Zhang; Jia Lyu; Yihua Wang; Shaolu Zhao; Weiwei Ma; Huan Zhang; Liwei Wang; Chunming Wang; et al. (Planta, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Locally adaptive linear mixture model-based super-resolution land-cover mapping based on a structure tensor - Xiaodong Li; Yun Du; Feng Ling; Wenbo Li (International Journal of Remote Sensing, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Three new sulphur glycosides from the seeds of Descurainia sophia - Wei-sheng Feng; Chun-Ge Li; Xiao-Ke Zheng; Ling-Ling Li; Wen-Jing Chen; Yan-Li Zhang; Yan-Gang Cao; Jian-Hong Gong; Hai-Xue Kuang (Natural Product Research, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Identifying minimal hepatic encephalopathy in cirrhotic patients by measuring spontaneous brain activity - Hua-Jun Chen; Ling Zhang; Long-Feng Jiang; Qiu-Feng Chen; Jun Li; Hai-Bin Shi (Metabolic Brain Disease, 2016)

Investigation of diarrhetic shellfish toxins in Lingshan Bay, Yellow Sea, China, using solid-phase adsorption toxin tracking (SPATT) - Feng-Ling Li; Zhao-Xin Li; Meng-Meng Guo; Hai-Yan Wu; Ting-Ting Zhang; Cai-Hu Song (Food Additives & Contaminants: Part A, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

Spatial and temporal variation of drought index in a typical steep alpine terrain in Hengduan Mountains - Gno-feng Zhu; Ling Yang; Da-he Qin; Hua-li Tong; Yuan-feng Liu; Jia-fang Li (Journal of Mountain Science, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Improving super-resolution mapping through combining multiple super-resolution land-cover maps - Xiaodong Li; Feng Ling; Giles M. Foody; Yun Du (International Journal of Remote Sensing, 2016)

Interferon-inducible GTPase: a novel viral response protein involved in rabies virus infection - Ling Li; Hualei Wang; Hongli Jin; Zengguo Cao; Na Feng; Yongkun Zhao; Xuexing Zheng; Jianzhong Wang; Qian Li; Guoxing Zhao; Feihu Yan; Lina Wang; et al. (Archives of Virology, 2016)

Visual detection of Ebola virus using reverse transcription loop-mediated isothermal amplification combined with nucleic acid strip detection - Changping Xu; Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Zengguo Cao; Ling Li; Jianzhong Wang; Feihu Yan; Lina Wang; Hang Chi; Weiwei Gai; et al. (Archives of Virology, 2016)

Characterization, expression, and functional analysis of testis-specific serine/threonine kinase 1 ( Tssk1 ) in the pen shell Atrina pectinata - Hao-Hao Li; Ling-Feng Kong; Ruihai Yu; Hong Yu; Qi Li (Invertebrate Reproduction & Development, 2016)

MicroRNA-25 Negatively Regulates Cerebral Ischemia/Reperfusion Injury-Induced Cell Apoptosis Through Fas/FasL Pathway - Jun-feng Zhang; Li-li Shi; Li Zhang; Zhao-hua Zhao; Fei Liang; Xi Xu; Ling-yu Zhao; Peng-bo Yang; Jian-shui Zhang; Ying-fang Tian (Journal of Molecular Neuroscience, 2016)

Prestack migration velocity analysis based on simplified two-parameter moveout equation - Hai-Feng Chen; Xiang-Yang Li; Zhong-Ping Qian; Jian-Jun Song; Gui-Ling Zhao (Applied Geophysics, 2016)

Chemical composition and antioxidant activities of the essential oil from Nandina domestica fruits - Shu-Feng Bi; Guang-Qi Zhu; Jie Wu; Zhong-Kang Li; Yong-Zhan Lv; Ling Fang (Natural Product Research, 2016)

Association between the methylenetetrahydrofolate reductase c.677C>T polymorphism and bone mineral density: an updated meta-analysis - Hong-Zhuo Li; Wei Wang; Yi-Ling Liu; Xiao-Feng He (Molecular Genetics and Genomics, 2016)

Novel predictors of soil genesis following natural weathering processes of bauxite residues - Feng Zhu; Shengguo Xue; William Hartley; Ling Huang; Chuan Wu; Xiaofei Li (Environmental Science and Pollution Research, 2016)

Isolation and sequence analysis of the complete NS1 and VP2 genes of canine parvovirus from domestic dogs in 2013 and 2014 in China - Hualei Wang; Hongli Jin; Qian Li; Guoxing Zhao; Nan Cheng; Na Feng; Xuexing Zheng; Jianzhong Wang; Yongkun Zhao; Ling Li; Zengguo Cao; Feihu Yan; et al. (Archives of Virology, 2016)

Rat Liver Mitochondrial Dysfunction Induced by an Organic Arsenical Compound 4-(2-Nitrobenzaliminyl) Phenyl Arsenoxide - Yuan-Hong Jiao; Qian Zhang; Ling-Li Pan; Xin-You Chen; Ke-Lin Lei; Jie Zhao; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2015)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Recursive impedance inversion of ground-penetrating radar data in stochastic media - Zhao-Fa Zeng; Xiong Chen; Jing Li; Ling-Na Chen; Qi Lu; Feng-Shan Liu (Applied Geophysics, 2015)

Major and trace elements of abyssal peridotites: evidence for melt refertilization beneath the ultraslow-spreading Southwest Indian Ridge (53° E segment) - Ling Chen; Feng-You Chu; Ji-Hao Zhu; Yan-Hui Dong; Xing Yu; Zheng-Gang Li; Li-Mei Tang (International Geology Review, 2015)

Lipoic acid protects dopaminergic neurons in LPS-induced Parkinson’s disease model - Yan-Hua Li; Qing He; Jie-zhong Yu; Chun-yun Liu; Ling Feng; Zhi Chai; Qing Wang; Hong-zhen Zhang; Guang-Xian Zhang; Bao-guo Xiao; Cun-gen Ma (Metabolic Brain Disease, 2015)

Anatomic Structure and Expression Profiles of Related Genes: Novel Insights into Leaf Development in Celery - Xiao-Ling Jia; Guang-Long Wang; Feng Wang; Yan Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Journal of Plant Growth Regulation, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Geochemical constraints on the contribution of Louisville seamount materials to magmagenesis in the Lau back-arc basin, SW Pacific - Zheng-Gang Li; Feng-You Chu; Yan-Hui Dong; Ji-Qiang Liu; Ling Chen (International Geology Review, 2015)

Spectral–spatial based sub-pixel mapping of remotely sensed imagery with multi-scale spatial dependence - Yihang Zhang; Yun Du; Feng Ling; Xia Wang; Xiaodong Li (International Journal of Remote Sensing, 2015)

Non-isothermal kinetic analysis of thermal decomposition of the Ca-bentonite from Santai, China - Xiang-hui Zhang; Chuan He; Ling Wang; Zhong-quan Li; Miao Deng; Jing Liu; Hong-kui Li; Qian Feng (Mineralogy and Petrology, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Using rabies virus vaccine strain SRV9 as viral vector to express exogenous gene - Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Ling Li; Yinglin Qi; Meng Liang; Yongkun Zhao; Tiecheng Wang; Yuwei Gao; Changchun Tu; Ningyi Jin; et al. (Virus Genes, 2015)

Comparative analysis of selected innate immune-related genes following infection of immortal DF-1 cells with highly pathogenic (H5N1) and low pathogenic (H9N2) avian influenza viruses - Ai-ling Liu; Yu-feng Li; Wenbao Qi; Xiu-li Ma; Ke-xiang Yu; Bing Huang; Ming Liao; Feng Li; Jie Pan; Min-xun Song (Virus Genes, 2015)

Insufficient secretion of IL-10 by Tregs compromised its control on over-activated CD4+ T effector cells in newly diagnosed adult immune thrombocytopenia patients - Feng Li; Lili Ji; Weiguang Wang; Fanli Hua; Yanxia Zhan; Shanhua Zou; Ling Yuan; Yang Ke; Zhihui Min; Dongli Song; Lihua Sun; Hao Chen; et al. (Immunologic Research, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

The decreased frequency of SIGIRR-positive CD4+ T cells in peripheral blood of patients with SLE and its correlation with disease activity - Dao-Yang Wang; Chao Su; Gui-Mei Chen; Hai-Feng Pan; Feng-Mei Wang; Gui-Ling Liu; Li Hao; De-Guang Wang; Dong-Qing Ye (Molecular Biology Reports, 2015)

Mesenchymal stem cells alleviate atherosclerosis by elevating number and function of CD4+CD25+FOXP3+ regulatory T-cells and inhibiting macrophage foam cell formation - Zhi Xiao Wang; Chong Quan Wang; Xiao Yan Li; Gao Ke Feng; Hong Ling Zhu; Yan Ding; Xue Jun Jiang (Molecular and Cellular Biochemistry, 2015)

Isolation and genetic characterization of avian influenza virus H4N6 from ducks in China - Xiao-yuan Yuan; You-ling Wang; Ke-Xiang Yu; Yu-xia Zhang; Huai-ying Xu; Jin-xing Yang; Feng Li; Min-xun Song (Archives of Virology, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Rearrangement structure-independent strategy of CNV breakpoint analysis - Jianqiu Xiao; Ling Zhang; Jingmin Wang; Yuwu Jiang; Lirong Jin; Jianqi Lu; Li Jin; Chunjiu Zhong; Xiangmin Xu; Feng Zhang (Molecular Genetics and Genomics, 2014)

Post-processing of interpolation-based super-resolution mapping with morphological filtering and fraction refilling - Feng Ling; Shiming Fang; Wenbo Li; Xiaodong Li; Fei Xiao; Yihang Zhang; Yun Du (International Journal of Remote Sensing, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Berberine reduces ischemia/reperfusion-induced myocardial apoptosis via activating AMPK and PI3K–Akt signaling in diabetic rats - Keke Chen; Guohua Li; Fenghao Geng; Zhao Zhang; Jiani Li; Min Yang; Ling Dong; Feng Gao (Apoptosis, 2014)

A new modified sesquiterpene glycoside from Cupressus chengiana - Yan Lin; Rong-Jiao Li; Yan Li; Brian D. McGarvey; Hai-Feng Wu; Xiao-Ling Wang (Natural Product Research, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Berberine regulates the expression of E-prostanoid receptors in diabetic rats with nephropathy - Li Qin Tang; Sheng Liu; Shan Tang Zhang; Ling Na Zhu; Feng Ling Wang (Molecular Biology Reports, 2014)

Improved yield and Zn accumulation for rice grain by Zn fertilization and optimized water management - Yu-yan Wang; Yan-yan Wei; Lan-xue Dong; Ling-li Lu; Ying Feng; Jie Zhang; Feng-shan Pan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Physiological and morphological responses to the first bout of refeeding in southern catfish (Silurus meridionalis) - Ling-Qing Zeng; Shi-Jian Fu; Xiu-Ming Li; Feng-Jie Li; Bin Li; Zhen-Dong Cao; Yao-Guang Zhang (Journal of Comparative Physiology B, 2014)

Development, inheritance and evaluation of 55 novel single nucleotide polymorphism markers for parentage assignment in the Pacific oyster (Crassostrea gigas) - Yu-Lin Jin; Ling-Feng Kong; Hong Yu; Qi Li (Genes & Genomics, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Preparation of transgenic Dunaliella salina for immunization against white spot syndrome virus in crayfish - Shuying Feng; Wenpo Feng; Ling Zhao; Huihui Gu; Qinghua Li; Ke Shi; Sanxing Guo; Nannan Zhang (Archives of Virology, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

Thermosensitive mPEG-b-PA-g-PNIPAM Comb Block Copolymer Micelles: Effect of Hydrophilic Chain Length and Camptothecin Release Behavior - Xiao-Li Yang; Yan-Ling Luo; Feng Xu; Ya-Shao Chen (Pharmaceutical Research, 2014)

GNSS ambiguity resolution with controllable failure rate for long baseline network RTK - Bofeng Li; Yunzhong Shen; Yanming Feng; Weiguang Gao; Ling Yang (Journal of Geodesy, 2014)

Giant plagioclase growth during storage of basaltic magma in Emeishan Large Igneous Province, SW China - Li-Lu Cheng; Zong-Feng Yang; Ling Zeng; Yu Wang; Zhao-Hua Luo (Contributions to Mineralogy and Petrology, 2014)

Three new olean-type triterpenoid saponins from aerial parts of Eclipta prostrata (L.) - Feng-Min Xi; Chun-Tong Li; Jun-Ling Mi; Zhi-Jun Wu; Wan-Sheng Chen (Natural Product Research, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Association between the TP53 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Zhi-Bin Bu; Jie Feng; Ling Peng; Xin-Biao Liao; Xin-Li Zhu; Xiao-li Sun; Hao-Gang Yu; Dan-Fang Yan; Sen-Xiang Yan (Molecular Biology Reports, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

MicroRNA-29a protects against acute liver injury in a mouse model of obstructive jaundice via inhibition of the extrinsic apoptosis pathway - Mao-Meng Tiao; Feng-Sheng Wang; Li-Tung Huang; Jiin-Haur Chuang; Ho-Chang Kuo; Ya-Ling Yang; Ying-Hsien Huang (Apoptosis, 2014)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Genetic and epigenetic variation in mass selection populations of Pacific oyster Crassostrea gigas - Qun Jiang; Qi Li; Hong Yu; Ling-Feng Kong (Genes & Genomics, 2013)

qLTG-9, a stable quantitative trait locus for low-temperature germination in rice (Oryza sativa L.) - Linfang Li; Xi Liu; Kun Xie; Yihua Wang; Feng Liu; Qiuyun Lin; Wenyan Wang; Chunyan Yang; Bingyue Lu; Shijia Liu; Liangming Chen; Ling Jiang; et al. (Theoretical and Applied Genetics, 2013)

Robust adaptive polarization analysis method for eliminating ground roll in 3C land seismics - Hai-Feng Chen; Xiang-Yang Li; Zhong-Ping Qian; Gui-Ling Zhao (Applied Geophysics, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Revealing storage-area relationship of open water in ungauged subalpine wetland — Napahai in Northwest Yunnan, China - Jie Li; Jin-ming Hu; Wei Deng; Sheng-li Huang; Hai-feng Jia; Chun-ling Zhu; Huai-xiu Luo (Journal of Mountain Science, 2013)
Mountains and plateaus in Southwest China contain many subalpine and alpine wetlands, with significant hydroecological functions. But ungauged or poorly gauged conditions limit the study and understanding of hydrological regimes of these wetland types. This study selects an ungauged subalpine wetland — Napahai in Northwest Yunnan, China — as a case for developing a practical approach to revealing its storage-area relationship of open water. A Trimble R8 GNSS (Global Navigation Satellites Systems) RTK (Real-time Kinematic system) and sonar fathometer were used to survey fine-resolution elevation data and generate a digital elevation model of the Napahai Wetland. Forty-four Landsat images from 1987 to 2011 were collected, and the Normalized Difference Water Index was used to classify open water features in the area. The area of open water in Napahai was calculated for each phase. With these data and a developed conceptual model, the storage of open water for each phase was estimated using ArcGIS tools. Both storage and area of open water showed significant intra-annual and inter-annual variations. In the rainy season, the monthly change of average storage of open water in Napahai showed about 1–2 months lag behind mean monthly rainfall. The storage-area relationship of open water was well fit by a power function equation ( R 2 ≈0.91, n =44). This study indicates that if detailed elevations are available for similarly ungauged subalpine wetlands in Southwest China, researchers can use this practical approach to estimate multi-temporal areas and storages and reveal the storage-area relationship of open water in the wetlands. The study provided valuable information of this case wetland for optimizing its hydro-ecological managements and a new method to wetland researchers and managers for the hydrological study of similarly ungauged wetland complex.

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Berberine ameliorates renal injury by regulating G proteins-AC- cAMP signaling in diabetic rats with nephropathy - Li Qin Tang; Feng Ling Wang; Ling Na Zhu; Fei Lv; Sheng Liu; Shan Tang Zhang (Molecular Biology Reports, 2013)

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts - Yuan-yuan Yao; Man-hua Zhu; Feng-jiang Zhang; Chuan-yun Wen; Lei-lei Ma; Wen-na Wang; Can-can Wang; Xian-bao Liu; Li-na Yu; Ling-bo Qian; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2013)

Analysis of genetic diversity of Ruthenia Medic (Medicago ruthenica (L.) Trautv.) in Inner Mongolia using ISSR and SSR markers - Hong-yan Li; Zhi-yong Li; Li-yan Cai; Wen-gui Shi; Fu-gui Mi; Feng-ling Shi (Genetic Resources and Crop Evolution, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Enhanced differentiation potential of human amniotic mesenchymal stromal cells by using three-dimensional culturing - Xue Lin; Hao Yu Li; Lian Feng Chen; Bo Jiang Liu; Yian Yao; Wen Ling Zhu (Cell and Tissue Research, 2013)

Sequence and phylogenetic analysis of nucleocapsid genes of porcine epidemic diarrhea virus (PEDV) strains in China - Zhili Li; Feng Chen; Yao Yuan; Xiduo Zeng; Zhongyan Wei; Ling Zhu; Baoli Sun; Qingmei Xie; Yongchang Cao; Chunyi Xue; Jingyun Ma; Yingzuo Bee (Archives of Virology, 2013)

Enhanced Photocatalytic Activities of Multi-Modified TiO2 Films on Common Glass Substrates - Fang Li; Nan Zhao; Ling-xiao Guan; Ji-jun Feng; Ming-ming Yao (Water, Air, & Soil Pollution, 2013)

Synthesis and insect antifeedant activity of stilbene derivatives against Brontispa longissima Larvae - Ying-Qian Liu; Xiao-Jing Li; Chun-Yan Zhao; Yan Lu; Wen-Qun Li; Zhen-Ling Liu; Gang Feng; Liu Yang (Medicinal Chemistry Research, 2013)

Extracellular Signal-Regulated Kinase 5 in the Cerebrospinal Fluid-Contacting Nucleus Contributes to Morphine Physical Dependence in Rats - Chun-Guang Wang; Yan-Ling Ding; Tian-Fang Zheng; Jing-Qiu Wei; He Liu; Yu-Feng Chen; Jia-You Wang; Li-Cai Zhang (Journal of Molecular Neuroscience, 2013)

Potential Prevention and Treatment of Maifanite for Alzheimer's Disease Based on Behavior Test, Oxidative Stress Assay, and Trace Element Analysis in Hippocampus of Aβ(25–35)-Induced AD Rats - Ling-Feng Jiang; Hai-Lin Liao; Hong-Miao Huang; Li-Xia Zhou; Ling Li; Shi-Xian Cheng; Cheng-Zhi Du (Biological Trace Element Research, 2013)

Renoprotective effects of berberine and its possible molecular mechanisms in combination of high-fat diet and low-dose streptozotocin-induced diabetic rats - Feng Ling Wang; Li Qin Tang; Feng Yang; Ling Na Zhu; Ming Cai; Wei Wei (Molecular Biology Reports, 2013)

A non-synonymous SNP in the NOS2 associated with septic shock in patients with sepsis in Chinese populations - Zhifu Wang; Kai Feng; Maoxing Yue; Xiaoguang Lu; Qihan Zheng; Hongxing Zhang; Yun Zhai; Peiyao Li; Lixia Yu; Mi Cai; Xiumei Zhang; Xin Kang; et al. (Human Genetics, 2013)

Isolation and characterization of microsatellite loci in the clam Lutraria sieboldii Reeve (Bivalvia: Veneroida) - Xiang-Ju Su; Ying Pan; Zi-Rong Zuo; Ling-Feng Kong; Qi Li (Conservation Genetics Resources, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

SOD1 gene transfer into paraventricular nucleus attenuates hypertension and sympathetic activity in spontaneously hypertensive rats - Ning Yuan; Feng Zhang; Ling-Li Zhang; Juan Gao; Ye-Bo Zhou; Ying Han; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Expression of survivin and patients survival in non-small cell lung cancer: a meta-analysis of the published studies - Li-nian Huang; Dong-sheng Wang; Yu-qing Chen; Cheng-ling Zhao; Bei-lei Gong; An-bang Jiang; Wei Jia; Feng-dan Hu (Molecular Biology Reports, 2013)

Sub-pixel mapping of remotely sensed imagery with hybrid intra- and inter-pixel dependence - Feng Ling; Xiaodong Li; Yun Du; Fei Xiao (International Journal of Remote Sensing, 2013)

Binding properties of Ru(II) polypyridyl complexes with poly(U)·poly(A)*poly(U) triplex: the ancillary ligand effect on third-strand stabilization - Li-Feng Tan; Ling-Jun Xie; Xiao-Nan Sun (JBIC Journal of Biological Inorganic Chemistry, 2013)

Spatially adaptive smoothing parameter selection for Markov random field based sub-pixel mapping of remotely sensed images - Xiaodong Li; Yun Du; Feng Ling (International Journal of Remote Sensing, 2012)

TNFAIP1 interacts with KCTD10 to promote the degradation of KCTD10 proteins and inhibit the transcriptional activities of NF-κB and AP-1 - Xiang Hu; Feng Yan; Fangmei Wang; Zijian Yang; Ling Xiao; Li Li; Shuanglin Xiang; Jianlin Zhou; Xiaofeng Ding; Jian Zhang (Molecular Biology Reports, 2012)

General framework and key issues concerning integrated strategies for coping with drought and flood in China in a changing environment - Deng-Hua Yan; Jing Feng; Chuan-Zhe Li; Tian-Ling Qin; Bai-Sha Weng; Xin Jin (Natural Hazards, 2012)

Effect of feeding on the function and structure of the digestive system in juvenile southern catfish (Silurus meridionalis Chen) - Ling-Qing Zeng; Feng-Jie Li; Shi-Jian Fu; Zhen-Dong Cao; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

The connection between GRKs and various signaling pathways involved in diabetic nephropathy - Feng-Ling Wang; Li-Qin Tang; Wei Wei (Molecular Biology Reports, 2012)

Construction of an infectious clone of human adenovirus type 41 - Duo-Ling Chen; Liu-Xin Dong; Meng Li; Xiao-Juan Guo; Min Wang; Xin-Feng Liu; Zhuo-Zhuang Lu; Tao Hung (Archives of Virology, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Isolation and Characterization of a Temperature-Regulated Microsomal Oleate Desaturase Gene (CtFAD2-1) from Safflower (Carthamus tinctorius L.) - Ling-Liang Guan; Ying-Wen Xu; Yuan-Biao Wang; Li Chen; Jin-feng Shao; Wei Wu (Plant Molecular Biology Reporter, 2012)

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain - Ying Han; Yan Li; Xing Xiao; Jia Liu; Xiang-Ling Meng; Feng-Yu Liu; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2012)

Larval settlement and metamorphosis of the mussel Mytilus coruscus in response to natural biofilms - Chong Wang; Wei-Yang Bao; Zhong-Qi Gu; Yi-Feng Li; Xiao Liang; Yun Ling; Sheng-Li Cai; He-Ding Shen; Jin-Long Yang (Biofouling, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Key parameter optimization and analysis of stochastic seismic inversion - Zhe-Yuan Huang; Li-Deng Gan; Xiao-Feng Dai; Ling-Gao Li; Jun Wang (Applied Geophysics, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Optimization of media composition and culture conditions for acarbose production by Actinoplanes utahensis ZJB-08196 - Ya-Jun Wang; Li-Ling Liu; Zhi-Hua Feng; Zhi-Qiang Liu; Yu-Guo Zheng (World Journal of Microbiology and Biotechnology, 2011)

Cloning and Characterization of the H Subunit of a Magnesium Chelatase Gene (PpCHLH) in Peach - Hai-Feng Jia; Ye-Mao Chai; Chun-Li Li; Ling Qin; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2011)

QTL mapping of bio-energy related traits in Sorghum - Yan-an Guan; Hai-lian Wang; Ling Qin; Hua-wen Zhang; Yan-bing Yang; Feng-ju Gao; Ru-yu Li; Hong-gang Wang (Euphytica, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Effects of rhizobial inoculation, cropping systems and growth stages on endophytic bacterial community of soybean roots - Yun Zeng Zhang; En Tao Wang; Mao Li; Qin Qin Li; Yan Ming Zhang; Shuang Jin Zhao; Xiu Ling Jia; Li Hua Zhang; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2011)

Two new 3-oxo-α-ionol glucosides from Urtica laetevirens Maxim. - Yuan Zhou; Bao-Min Feng; Li-Ying Shi; Hui-Guo Wang; Ling Tang; Yong-Qi Wang (Natural Product Research, 2011)

Analysis of 19-nortestosterone residue in animal tissues by ion-trap gas chromatography-tandem mass spectrometry - Jin-qing Jiang; Lei Zhang; Guang-ling Li; Hai-tang Zhang; Xue-feng Yang; Jun-wei Liu; Ren-feng Li; Zi-liang Wang; Jian-hua Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Characterization of 68Zn uptake, translocation, and accumulation into developing grains and young leaves of high Zn-density rice genotype - Chun-yong Wu; Ying Feng; Md. Jahidul Islam Shohag; Ling-li Lu; Yan-yan Wei; Chong Gao; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2011)

Variations of PM10 concentrations in Wuhan, China - Qi Feng; Shengjun Wu; Yun Du; Xiaodong Li; Feng Ling; Huaiping Xue; Shuming Cai (Environmental Monitoring and Assessment, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Cloning and Expression Analysis of Wheat Cytokinin Oxidase/Dehydrogenase Gene TaCKX3 - Xin Ma; De-Shun Feng; Hong-Gang Wang; Xing-Feng Li; Ling-Rang Kong (Plant Molecular Biology Reporter, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

A nested PCR assay targeting the DNA topoisomerase I gene to detect the pine wood nematode, Bursaphelenchus xylophilus - Lin Huang; Xu-ling Xu; Xiao-qin Wu; Feng-mao Chen; Chao Li; Jian-ren Ye (Phytoparasitica, 2010)

Characterization of thirteen single nucleotide polymorphism markers in the sea cucumber (Apostichopus japonicus) - Wen-Jing Sun; Qi Li; Ling-Feng Kong (Conservation Genetics Resources, 2010)

Development and characterization of 14 polymorphic microsatellite loci in the razor clam (Sinonovacula constricta) - Qun Jiang; Qi Li; Yang Yuan; Ling-Feng Kong (Conservation Genetics Resources, 2010)

Fractions and leaching characteristics of mercury in coal - Chun-Gang Yuan; Qing-Peng Li; Ya-Na Feng; Ai-Ling Chang (Environmental Monitoring and Assessment, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

Twenty microsatellite DNA markers for the Venus clam (Cyclina sinensis Gmelin) - Yan-Wei Feng; Qi Li; Ling-Feng Kong (Conservation Genetics, 2010)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Cloning and Characterization of Functional Trehalose-6-Phosphate Synthase Gene in Maize - Wei Jiang; Feng-Ling Fu; Su-Zhi Zhang; Ling Wu; Wan-Chen Li (Journal of Plant Biology, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Secretion of citrate from roots in response to aluminum and low phosphorus stresses in Stylosanthes - Xiao Feng Li; Fang Hua Zuo; Gui Zhi Ling; Yao Yan Li; Yong Xiong Yu; Pei Quan Yang; Xing Lian Tang (Plant and Soil, 2009)

Isolation and characterization of microsatellite loci in the horseshoe crab (Tachypleus tridentatus) - Qiong-Zhen Li; Qi Li; Jun Liu; Le-Hai Ni; Ling-Feng Kong (Conservation Genetics, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Isolation and characterization of microsatellite loci in the tuba false fusus (Hemifusus tuba Gmelin) - Yang Yuan; Qi Li; Ying Pan; Ling-Feng Kong (Conservation Genetics Resources, 2009)

A novel method for promoting conidial production by a nematophagous fungus, Pochonia chlamydosporia AS6.8 - Ling-Ling Xu; Feng Li; Hong-Yan Xie; Xing-Zhong Liu (World Journal of Microbiology and Biotechnology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Isolation and characterization of 13 microsatellite loci in the pen shell Atrina pectinata (Bivalvia: Pinnidae) - Jun Liu; Qi Li; Ling-Feng Kong (Conservation Genetics, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Adsorption of lead(II) from aqueous solution onto Hydrilla verticillata - Ling-zhi Huang; Guang-ming Zeng; Dan-lian Huang; Li-feng Li; Peng-mian Huang; Chang-bin Xia (Biodegradation, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of 14 polymorphic microsatellite loci in the ark shell Scapharca subcrenata (Bivalvia: Arcidae) - Yan-Wei Feng; Qi Li; Ling-Feng Kong (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

The mouse Pol I terminator is more efficient than the hepatitis delta virus ribozyme in generating influenza-virus-like RNAs with precise 3′ ends in a plasmid-only-based virus rescue system - Liqiang Feng; Feng Li; Xuehua Zheng; Weiqi Pan; Kai Zhou; Yichu Liu; Hongxuan He; Ling Chen (Archives of Virology, 2009)

Long-term treatment of l-3-n-butylphthalide attenuated neurodegenerative changes in aged rats - Shiping Ma; Shaofeng Xu; Bin Liu; Jiang Li; Nan Feng; Ling Wang; Xiaoliang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Isolation and characterization of microsatellite loci in endangered Cycas changjiangensis (Cycadaceae) - Ling Li; Zheng-Feng Wang; Shu-Guang Jian; Peng Zhu; Min Zhang; Wan-Hui Ye; Hai Ren (Conservation Genetics, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

Lignan and flavonoid glycosides from Urtica laetevirens Maxim. - Yuan Zhou; Wei Wang; Ling Tang; Xing-guo Yan; Li-ying Shi; Yong-qi Wang; Bao-min Feng (Journal of Natural Medicines, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Using an Inverse PCR Method to Clone the Wheat Cytokinin Oxidase/Dehydrogenase Gene TaCKX1 - De-Shun Feng; Hong-Gang Wang; Xian-Sheng Zhang; Ling-Rang Kong; Ji-Chun Tian; Xing-Feng Li (Plant Molecular Biology Reporter, 2008)

Availability and toxicity of Fe(II) and Fe(III) in Caco-2 cells - Wan-ling He; Ying Feng; Xiao-li Li; Yan-yan Wei; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

The value of endoscopic ultrasonography on diagnosis and treatment of esophageal hamartoma - Guo-qiang Xu; Feng-ling Hu; Li-hua Chen; Guo-dong Shan; Bing-ling Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Altered gene expression of NIDD in dorsal root ganglia and spinal cord of rats with neuropathic or inflammatory pain - Meng-Ling Chen; Chun Cheng; Qing-Shan Lv; Zhi-Qin Guo; Ying Gao; Shang-Feng Gao; Xin Li; Shu-Qiong Niu; Shu-Xian Shi; Ai-Guo Shen (Journal of Molecular Histology, 2008)

Isolation and characterization of microsatellite loci in the xishishe clam Coelomactra antiquata (Bivalvia: Veneroida) - Jing-Jing Li; Qi Li; Ling-Feng Kong (Conservation Genetics, 2008)

Viral protein synthesis is required for Enterovirus 71 to induce apoptosis in human glioblastoma cells - Shin-Ru Shih; Kuo-Feng Weng; Victor Stollar; Mei-Ling Li (Journal of NeuroVirology, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

A novel tissue array technique for high-throughput tissue microarray analysis — microarray groups - Hui-Yong Jiang; Xue-Feng Zhang; Li Liu; Hui-Ling Li; Tong Zhao (In Vitro Cellular & Developmental Biology - Animal, 2007)

EFFECT OF EXOGENOUS WILD-TYPE P53 ON MELANOMA CELL DEATH PATHWAYS INDUCED BY IRRADIATION AT DIFFERENT LINEAR ENERGY TRANSFER - FENG-LING MIN; HONG ZHANG; WEN-JIAN LI; QING-XIANG GAO; GUANG-MING ZHOU (In Vitro Cellular & Developmental Biology - Animal, 2005)

EFFECT OF EXOGENOUS WILD TYPE P53 ON MELANOMA CELL DEATH PATHWAYS INDUCED BY IRRADIATION AT DIFFERENT LET - Feng-ling MIN; HONG ZHANG; Wen-jian LI; Qing-xiang Gao (In Vitro Cellular & Developmental Biology - Animal, 2005)

Development of mariculture and its impacts in Chinese coastal waters - Yang Yu Feng; Li Chun Hou; Nie Xiang Ping; Tang Dan Ling; Chung Ik Kyo (Reviews in Fish Biology and Fisheries, 2004)

Variations of stomatal density and carbon isotope values of Picea crassifolia at different altitudes in the Qilian Mountains - Wei-ya Qiang; Xun-ling Wang; Tuo Chen; Hu-yuan Feng; Li-zhe An; Yuan-qin He; Gang Wang (Trees, 2003)

Ri-mediated transformation of Artemisia annua with a recombinant farnesyl diphosphate synthase gene for artemisinin production - Da-Hua Chen; Chang-Jun Liu; He-Chun Ye; Guo-Feng Li; Ben-Ye Liu; Yu-Ling Meng; Xiao-Ya Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)